Glass for chemical strengthening and glass

By adjusting the composition ratio and chemical strengthening treatment of Li2O-Al2O3-SiO2 chemically strengthened glass, the problem of difficulty in balancing multiple properties of chemically strengthened glass in the existing technology is solved, and high strength, scratch resistance, charging characteristics and low Effect of viscosity.

CN119365428APending Publication Date: 2025-01-24AGC INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380046588.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-27
Filing Date
2023-06-09
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

While improving the strength of existing chemically reinforced glasses, it is difficult to take into account the requirements of transparency, scratch resistance, charging characteristics, and low viscosity and low melting temperature.

Method used

By adjusting the proportion of the ingredients in the glass of the Li2O-Al2O3-SIO2 chemical reinforcement, the total content of Al2O3 and Li2O is between 27%and 35%. And chemical strengthening to form a stress distribution of optimization.

Benefits of technology

Realize the chemical reinforced glass with high strength, 3D formability, charging characteristics, and excellent injury resistance, while reducing the viscosity and melting temperature, and meet the multiple performance requirements to protect the glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119365428A_ABST
    Figure CN119365428A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide a glass for chemical strengthening and a glass for obtaining a chemically strengthened glass having excellent strengthening characteristics and exhibiting characteristics suitable for cover glass. A glass for chemical strengthening, which contains, in mol% on the basis of oxides, 50% to 65% of SiO2, 15% to 23% of Al2O3, 2% to 10% of B2O3, 0% to 15% of P2O5, 0% to 15% of ZnO, 0% to 10% of MgO, 0% to 15% of CaO, 3% to 15% of Li2O, 2.5% to 15% of Na2O, 0% to 5% of K2O, 0% to 5% of ZrO2, 0% to 5% of Y2O3, and 0% to 5% of TiO2, with [Li2O] / ([Na2O] + [K2O]) being 0.5 to 3.5 and [Al2O3] + [Li2O] being 27% to 35%. In the formula, [] represents the content, in mol% on the basis of oxide, of each component described in the bracket.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to chemically strengthened glass and glass. Background Art

[0002] Glass used in protective glass of portable terminals, etc. is required to be high-strength, capable of 3D molding, and excellent in transparency, scratch resistance, and charging characteristics, etc. In addition, from the perspective of SDGs, there is an increasing demand for glass with low viscosity and low melting temperature.

[0003] As a method for increasing the strength of glass, a method of making chemically strengthened glass by subjecting the glass to ion exchange treatment can be cited. Chemically strengthened glass is glass that is formed on the surface of the glass by contacting the glass with a molten salt such as sodium nitrate to form an ion exchange between the alkali metal ions contained in the glass and the alkali metal ions with a larger ion radius contained in the molten salt. The strength of chemically strengthened glass strongly depends on the stress distribution represented by the compressive stress value with the depth from the glass surface as a variable.

[0004] Patent Document 1 describes a method of performing a two-step ion exchange treatment using chemically strengthened glass containing lithium. According to this method, a large compressive stress caused by sodium-potassium exchange can be generated in the surface portion of the glass, and a slightly smaller compressive stress caused by lithium-sodium exchange can be generated in the deeper portion.

[0005] On the other hand, when a compressive stress layer is formed on the surface of the glass, a tensile stress (hereinafter also referred to as CT) corresponding to the total amount of surface compressive stress is inevitably generated in the center of the glass. When the tensile stress value becomes too large, the glass article breaks violently and fragments fly. When CT exceeds its threshold value (hereinafter also referred to as CT limit), the number of fractures during damage increases explosively.

[0006] Therefore, chemically strengthened glass increases the compressive stress on the surface and forms a compressive stress layer to a deeper portion. On the other hand, the total amount of compressive stress in the surface layer is designed so as not to exceed the CT limit (hereinafter, when exceeding the CT limit, it is also simply referred to as exceeding the CT limit).

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application No. 2013-536155 Summary of the invention

[0010] Problems to be solved by the invention

[0011] As described above, the glass used for the cover glass is required to have high strength, be capable of 3D molding, be excellent in transparency, scratch resistance, and charging characteristics, and have low viscosity and low melting temperature.

[0012] It is generally believed that two important physical properties are essential for improving glass strength: (1) high fracture toughness and (2) excellent strengthening characteristics. As for the latter (2) strengthening characteristics, it is generally believed that the easier it is to strengthen through ion exchange treatment (the higher the surface compressive stress during chemical strengthening), the better.

[0013] However, the present inventors have repeatedly studied and found that there is an optimal range of strengthening characteristics when chemical strengthening is performed using sodium nitrate from the viewpoint of not exceeding the CT limit and ensuring drop strength.

[0014] Therefore, an object of the present invention is to provide chemically strengthened glass and glass for obtaining chemically strengthened glass having excellent strengthening properties and exhibiting properties suitable for cover glass.

[0015] Means used to solve problems

[0016] The above problems were studied, and as a result, a composition range satisfying the above characteristics was found in Li2O-Al2O3-SiO2-based chemically strengthened glass and chemically strengthened glass, thereby completing the present invention.

[0017] A first aspect of the present invention provides a chemically strengthened glass, wherein the chemically strengthened glass contains, in terms of mol % based on oxides:

[0018] 50%~65% SiO2,

[0019] 15% to 25% Al2O3,

[0020] 2% to 10% B2O3,

[0021] 0%~15% P2O5,

[0022] 0%~15% ZnO,

[0023] 0%~10%MgO,

[0024] 0%~15%CaO,

[0025] 3% to 15% Li2O,

[0026] 2.5% to 15% Na2O,

[0027] 0%~5% K2O,

[0028] 0%~5% ZrO2,

[0029] 0% to 5% Y2O3, and

[0030] 0%~5% TiO2,

[0031] [Li2O] / ([Na2O]+[K2O]) is 0.5 to 3.5,

[0032] [Al2O3]+[Li2O] is 27%~35%.

[0033] In the formula, [ ] represents the content of each component described in parentheses in terms of mol % based on oxides.

[0034] In addition, a second aspect of the present invention provides a glass comprising, in terms of mol % based on oxides:

[0035] 50%~65% SiO2,

[0036] 15% to 25% Al2O3,

[0037] 2% to 10% B2O3,

[0038] 0%~15% P2O5,

[0039] 0%~15% ZnO,

[0040] 0%~10%MgO,

[0041] 0%~15%CaO,

[0042] 3% to 15% Li2O,

[0043] 2.5% to 15% Na2O,

[0044] 0%~5% K2O,

[0045] 0%~5% ZrO2,

[0046] 0% to 5% Y2O3, and

[0047] 0%~5% TiO2,

[0048] [Li2O] / ([Na2O]+[K2O]) is 0.5 to 3.5,

[0049] [Al2O3]+[Li2O] is 27% to 35%,

[0050] The entropy function S value of the alkali ion represented by the following formula is 0.25 to 0.40.

[0051] S=-P Li ×log(PLi )-P Na ×log(P Na )-P K ×log(P K )

[0052] P Li =[Li2O] / ([Li2O]+[Na2O]+[K2O])

[0053] P Na =[Na2O] / ([Li2O]+[Na2O]+[K2O])

[0054] P K =[K2O] / ([Li2O]+[Na2O]+[K2O])

[0055] In the formula, [ ] represents the content of each component in parentheses in terms of mol % based on oxides.

[0056] In addition, a third aspect of the present invention provides a Li2O-Al2O3-SiO2-based chemically strengthened glass, wherein:

[0057] The Li2O-Al2O3-SiO2-based chemically strengthened glass contains 2% or more of B2O3, calculated as a mol% based on oxides.

[0058] The Li2O-Al2O3-SiO2-based chemically strengthened glass has a Young's modulus greater than 76 GPa,

[0059] When the Li2O-Al2O3-SiO2-based chemically strengthened glass is chemically strengthened at 380°C for 4 hours in 100% by mass sodium nitrate, the surface compressive stress CS0 is 200 MPa to 450 MPa and the compressive stress layer depth DOC is 70 μm to 120 μm.

[0060] The viscosity of the Li2O-Al2O3-SiO2 chemically strengthened glass reaches 10 2 The temperature (T2) at dPa·s is 1650°C or less.

[0061] A fourth aspect of the present invention provides a chemically strengthened glass, wherein the chemically strengthened glass contains, in terms of mol % based on oxides:

[0062] 50%~67% SiO2,

[0063] 16% to 25% Al2O3,

[0064] 2% to 10% B2O3,

[0065] 0%~15% P2O5,

[0066] 0%~15% ZnO,

[0067] 0%~10%MgO,

[0068] 0%~15%CaO,

[0069] 3% to 15% Li2O,

[0070] 2.5% to 15% Na2O,

[0071] 0%~5% K2O,

[0072] 0%~5% ZrO2,

[0073] 0% to 5% Y2O3, and

[0074] 0%~5% TiO2,

[0075] [Li2O] / ([Na2O]+[K2O]) is 0.5 to 3.5,

[0076] [Al2O3]+[Li2O] is 22% to 35%,

[0077] The Young's modulus of the chemically strengthened glass is 77 GPa or more.

[0078] In the formula, [ ] represents the content of each component described in parentheses in terms of mol % based on oxides.

[0079] In addition, a fifth aspect of the present invention provides a glass comprising, in terms of mol % based on oxides:

[0080] 50%~67% SiO2,

[0081] 16% to 25% Al2O3,

[0082] 2% to 10% B2O3,

[0083] 0%~15% P2O5,

[0084] 0%~15% ZnO,

[0085] 0%~10%MgO,

[0086] 0%~15%CaO,

[0087] 3% to 15% Li2O,

[0088] 2.5% to 15% Na2O,

[0089] 0%~5% K2O,

[0090] 0%~5% ZrO2,

[0091] 0% to 5% Y2O3, and

[0092] 0%~5% TiO2,

[0093] [Li2O] / ([Na2O]+[K2O]) is 0.5 to 3.5,

[0094] [Al2O3]+[Li2O] is 22% to 35%,

[0095] The Young's modulus of the glass is 77 GPa or more,

[0096] The entropy function S value of the alkali ion represented by the following formula is 0.25 to 0.40.

[0097] S=-P Li ×log(P Li )-P Na ×log(P Na )-P K ×log(P K )

[0098] P Li =[Li2O] / ([Li2O]+[Na2O]+[K2O])

[0099] P Na =[Na2O] / ([Li2O]+[Na2O]+[K2O])

[0100] P K =[K2O] / ([Li2O]+[Na2O]+[K2O])

[0101] In the formula, [ ] represents the content of each component in parentheses in terms of mol % based on oxides.

[0102] Effects of the Invention

[0103] The chemically strengthened glass of the first embodiment of the present invention satisfies a specific composition range, and in particular, the total content of Al2O3 and Li2O, and the ratio of the content of Li2O to the total content of Na2O and K2O are within a specific range. As a result, the fracture toughness and strengthening characteristics are excellent, so that a chemically strengthened glass having high strength, 3D formability, charging characteristics, and scratch resistance can be obtained, and the viscosity is low, so that it can be melted at a low temperature, and the amount of CO2 generated during production can be suppressed.

[0104] The glass of the second embodiment of the present invention satisfies a specific composition range, and in particular, the total content of Al2O3 and Li2O, the ratio of the content of Li2O to the total content of Na2O and K2O, and the entropy function value of alkali ions are within a specific range. Therefore, the glass of the present invention has excellent fracture toughness and strengthening characteristics, so it has high strength, and has excellent 3D formability, charging characteristics, and scratch resistance, and has low viscosity, so it can be melted at a low temperature, and the amount of CO2 generated during manufacturing can be suppressed.

[0105] The third formula of the present invention, Li2O-Al2O3-SiO2-based chemically strengthened glass, has a specific composition range and strengthening characteristics, and has low viscosity. Thus, the Li2O-Al2O3-SiO2-based chemically strengthened glass of the present invention can obtain chemically strengthened glass having excellent strength, 3D formability, charging characteristics, and scratch resistance, and can be melted at low temperatures, and the amount of CO2 generated during manufacturing can be suppressed.

[0106] The chemically strengthened glass of the fourth embodiment of the present invention satisfies a specific composition range, and in particular, the total content of Al2O3 and Li2O, and the ratio of the content of Li2O to the total content of Na2O and K2O are within a specific range. As a result, the fracture toughness and strengthening characteristics are excellent, so that a chemically strengthened glass having high strength, 3D formability, charging characteristics, and scratch resistance can be obtained, and the viscosity is low, so it can be melted at a low temperature, and the amount of CO2 generated during production can be suppressed.

[0107] The glass of the fifth embodiment of the present invention satisfies a specific composition range, and in particular, the total content of Al2O3 and Li2O, the ratio of the content of Li2O to the total content of Na2O and K2O, and the entropy function value of alkali ions are within a specific range. Therefore, the glass of the present invention has excellent fracture toughness and strengthening characteristics, so it has high strength, and has excellent 3D formability, charging characteristics, and scratch resistance, and has low viscosity, so it can be melted at a low temperature, and the amount of CO2 generated during manufacturing can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS

[0108] Figure 1 The horizontal axis is CS1 (the calculated value of the surface compressive stress CS0 when tempered in 100% NaNO3 salt at 380°C for 4 hours) and the stress distribution of the glass obtained by tempering the specific glass satisfying the composition of the present invention using 100% NaNO3 salt at 380°C in a manner that maximizes the CT within the range of the CT limit is shown. 50 (circle) and CS 90 The graph is a graph with the calculated values ​​of (quadrilateral) plotted as the vertical axis. The plate thickness is assumed to be 0.7 mm. The portion surrounded by the dotted line is the range showing the optimal stress characteristics.

[0109] Figure 2 This is a diagram showing the stress distribution of the chemically strengthened glass obtained by chemically strengthening the glass of Example 5.

[0110] Figure 3 This is an explanatory diagram of a sample used for measuring the fracture toughness value by the DCDC method.

[0111] Figure 4 This is a diagram showing a KI-v curve indicating the relationship between the stress intensity factor KI and the crack growth rate v, which is used in the measurement of the fracture toughness value by the DCDC method. DETAILED DESCRIPTION

[0112] In the present specification, “to” indicating a numerical range is used to mean that the numerical values ​​described before and after it are included as the lower limit and the upper limit, and unless otherwise specified, “to” is used in the present specification with the same meaning.

[0113] In this specification, "stress distribution" refers to a curve that represents the compressive stress value using the depth from the glass surface as a variable. In this specification, DOC is the depth from the glass surface of the portion where the stress is zero in the stress distribution. DOC can be estimated by thinning the cross section of the glass and analyzing the thinned sample using a birefringence imaging system. As a birefringence imaging system, there is, for example, the birefringence imaging system Abrio-IM manufactured by Tokyo Instruments Co., Ltd. In addition, DOC can also be estimated using scattered light photoelasticity. In this method, light is incident from the surface of the glass, and the stress distribution is measured to estimate DOC by analyzing the polarized light of the scattered light. "Internal tensile stress CT" refers to the tensile stress value at a depth of 1 / 2 of the thickness t of the glass.

[0114] In this specification, the stress distribution can be measured by a method of using an optical waveguide surface strain gauge and a birefringence strain gauge in combination or a method of using an optical waveguide surface strain gauge and a scattered light photoelastic strain gauge in combination.

[0115] It is known that the method using an optical waveguide surface stress meter can accurately measure the stress of glass in a short time. As an optical waveguide surface stress meter, there is FSM-6000 manufactured by Orihara Manufacturing Co., Ltd. When FSM-6000 is combined with the accompanying software Fsm-V, high-precision stress measurement can be performed.

[0116] However, in principle, the optical waveguide surface stress gauge can only measure stress when the refractive index decreases from the surface of the sample to the inside. In chemically strengthened glass, the layer obtained by replacing sodium ions inside the glass with potassium ions from the outside has a refractive index that decreases from the surface of the sample to the inside, so the stress can be measured using the optical waveguide surface stress gauge. However, the stress of the layer obtained by replacing lithium ions inside the glass with sodium ions from the outside cannot be measured using the optical waveguide surface stress gauge. Therefore, when a lithium-containing glass is subjected to an ion exchange treatment using a molten salt containing sodium, the depth (D ) at which the compressive stress value is zero as measured by the optical waveguide surface stress gauge is 0. K ) is not the true depth of the compressive stress layer.

[0117] The method using a birefringent stress gauge can measure stress regardless of the refractive index distribution. As a birefringent stress gauge, there is, for example, the birefringent imaging system Abrio-IM manufactured by Cri. However, in order to measure stress using a birefringent stress gauge, it is necessary to process the glass sample into a thin sheet for use. In particular, it is difficult to accurately process the edge portion, so it is difficult to accurately obtain the stress value near the glass surface. By combining it with an optical waveguide surface stress gauge, accurate stress measurement can be performed. An example of a scattered light photoelastic stress gauge is the SLP2000 manufactured by Orihara Manufacturing Co., Ltd. In this method, the stress inside the glass can be measured by analyzing the polarization characteristics of the weak scattered light emitted from the light passing through the inside of the glass. However, near the surface layer of the glass, the intensity of the scattered light in the outermost layer has a stronger influence than the intensity of the scattered light from the inside of the glass, so it is difficult to accurately measure the stress near the surface layer of the glass. By combining it with an optical waveguide surface stress gauge, accurate stress measurement can be performed.

[0118] In this specification, "chemically strengthened glass" refers to glass subjected to a chemical strengthening treatment, and "glass for chemical strengthening" refers to glass before subjected to a chemical strengthening treatment.

[0119] In this specification, the glass composition is expressed in mole % based on oxides. In addition, in this specification, "substantially free of" means that the impurities contained in the raw materials are below the level, that is, not intentionally contained. Specifically, for example, it is preferably less than 0.1% by mass, more preferably less than 0.05% by mass, and even more preferably less than 0.01% by mass.

[0120] (First method)

[0121] <Chemically strengthened glass>

[0122] (composition)

[0123] The chemically strengthened glass of the first embodiment (hereinafter sometimes referred to as the present strengthened glass) contains, in terms of mol% based on oxides:

[0124] 50%~65% SiO2,

[0125] 15% to 25% Al2O3,

[0126] 2% to 10% B2O3,

[0127] 0%~15% P2O5,

[0128] 0%~15% ZnO,

[0129] 0%~10%MgO,

[0130] 0%~15%CaO,

[0131] 3% to 15% Li2O,

[0132] 2.5% to 15% Na2O,

[0133] 0%~5% K2O,

[0134] 0%~5% ZrO2,

[0135] 0% to 5% Y2O3, and

[0136] 0%~5% TiO2,

[0137] [Li2O] / ([Na2O]+[K2O]) is 0.5 to 3.5,

[0138] [Al2O3]+[Li2O] is 27%~35%.

[0139] In the formula, [ ] represents the content of each component described in parentheses in terms of mol % based on oxides.

[0140] The tempered glass of the present invention having the above-mentioned composition can easily form a preferred stress distribution by chemical strengthening treatment, does not exceed the CT limit, and can ensure drop strength. Figure 1 The horizontal axis is CS1 (hereinafter, CS1 is also referred to as NaCS. CS1 is a calculated value of the surface compressive stress CS0 when the specific present tempered glass satisfying the above composition is tempered in 100% NaNO3 salt at 380°C for 4 hours.), and the stress distribution of the glass obtained by chemically tempering the specific present tempered glass satisfying the above composition using 100% NaNO3 salt at 380°C in a manner that maximizes CT within a range not exceeding the CT limit is CS1 as the horizontal axis. 50 (circle) and CS 90 The calculated value of (quadrilateral) is plotted as the vertical axis. The thickness of the glass plate in the calculation is assumed to be 0.7 mm.

[0141] exist Figure 1 In the range surrounded by the dotted line, the range showing the best stress characteristics is considered from the perspective of not exceeding the CT limit and ensuring the drop strength. The following is an explanation. CS 50 It is the compressive stress value at a depth of 50 μm from the glass surface, and is a value related to the strength when a portable terminal having chemically strengthened glass as a cover glass is dropped onto a ground with fine sand. 90 The compressive stress value at a depth of 90 μm from the glass surface is a value related to the strength of chemically strengthened glass when dropped onto a surface with coarse sand. As a strength test method for protective glass, there is a method of dropping the glass onto sandpaper to evaluate the strength. 50 Equivalent to the strength of #180 sandpaper, CS 90 Equivalent to the strength of #80 sandpaper.

[0142] Figure 1 It is shown that there is an optimal range of CS1 under the premise of a single chemical strengthening process using 100% NaNO3 salt at 380°C. When CS1 becomes higher, DOC becomes shallower due to the limitation of CT limit. That is, when CS1 is too high, the depth (DOC) from the glass surface, which is the point where compressive stress and tensile stress are balanced inside the glass, becomes shallower. As a result, glass with CS1 is more likely to have a lower surface area than glass with CT limit. 90 In addition, when CS1 is reduced, although DOC can be deepened, the stress in the entire area in the depth direction is reduced as a whole, and CS 50 and CS 90 As a result, for example, Figure 1 In the region where CS1 is greater than about 440MPa to 450MPa, CS 90 The value of CS1 is less than 50 MPa, and the strengthening characteristics are insufficient. In addition, in the region where CS1 is less than about 200 MPa, CS 50 Less than 120MPa, the strengthening properties are insufficient. Figure 1 In the range enclosed by the dotted line, CS 50 The value is 120MPa or more and CS 90 The value of is 50MPa or more, so the strengthening characteristics are excellent and it shows characteristics suitable for protective glass. Figure 1 The optimal range of CS1 is preferably 200 MPa to 450 MPa, and particularly preferably about 200 MPa to about 440 MPa.

[0143] It should be noted that Figure 1The results are limited to the results of a single chemical strengthening process (hereinafter referred to as one-step strengthening) using 100% NaNO3 salt at 380°C, but the CS1 index and its optimal range obtained here can also be applied to Figure 2 The design of the stress distribution (hereinafter referred to as two-step strengthening stress distribution) obtained by the secondary chemical strengthening process (hereinafter referred to as two-step strengthening) is shown.

[0144] Generally, for the two-step strengthening stress distribution, in most cases, in the first chemical strengthening process, a molten salt containing a large amount of NaNO3 salt is used to form a deep stress layer obtained by Na→Li exchange (exchange of Na ions in the molten salt with Li ions in the glass), and in the second strengthening process, a molten salt containing a large amount of KNO3 salt is used to form a surface stress layer obtained by K→Na exchange (exchange of K ions in the molten salt with Na ions in the glass). 50 , CS 90 The optimization of the deep stress layer obtained by Na→Li exchange in the first chemical strengthening process is important.

[0145] The method and concept of optimizing the chemical strengthening process are similar to those of the one-step strengthening using 100% NaNO3 salt at 380°C, so the index of CS1 and its optimal range can also be applied to the stress design of the two-step strengthening. That is, by using the surface CS when strengthened with 100% NaNO3 salt at 380°C for 4 hours as an index, the range of glass composition that is most suitable for the design of the two-step strengthening stress distribution can be selected.

[0146] In the present invention, according to Figure 1 The index is prepared based on the results of the glass cooled at a cooling rate of 0.5°C / min, but the obtained index can also be applied to the glass cooled at a cooling rate of 0.5°C / min to 1000°C / min. The present strengthened glass can achieve the best stress characteristics when chemically strengthened using sodium nitrate by satisfying the above composition range.

[0147] Hereinafter, the glass composition of the present tempering glass will be described.

[0148] SiO2 is a component constituting the skeleton of glass. In addition, SiO2 is a component that improves chemical durability and is a component that reduces the generation of cracks when the glass surface is damaged. In order to improve chemical durability, the content of SiO2 is 50% or more, preferably 52% or more, more preferably 54% or more, further preferably 55% or more, and particularly preferably 56% or more.

[0149] In order to make the meltability of the glass good, the content of SiO2 is 65% or less, preferably 62% or less, more preferably 60% or less, further preferably 59% or less, and particularly preferably 58% or less.

[0150] In order to improve the ion exchangeability during chemical strengthening, increase the surface compressive stress after strengthening, or to increase the glass transition temperature (Tg) and Young's modulus, the Al2O3 content is 15% or more, preferably 16% or more, more preferably 17% or more, further preferably 19% or more, particularly preferably 20% or more, and most preferably 20.5% or more.

[0151] In addition, when the content of Al2O3 is too much, the viscosity increases and the devitrification characteristics deteriorate. The content of Al2O3 is 25% or less, preferably 23% or less, more preferably 22% or less, and further preferably 21.5% or less.

[0152] When the content of B2O3 is small, the viscosity increases, and when the content of B2O3 is too high, the chemical resistance deteriorates. The content of B2O3 is 2% or more, preferably 2.5% or more, preferably 3% or more, more preferably 4% or more, and further preferably 5% or more. The content of B2O3 is 10% or less, preferably 9% or less, more preferably 8% or less, further preferably 7% or less, further preferably 6% or less, and particularly preferably 5.5% or less.

[0153] P2O5 may be contained in order to improve the ion exchange performance. When the content of P2O5 is small, the viscosity increases, and when the content of P2O5 is too much, the chemical resistance deteriorates. In the case of containing P2O5, the content of P2O5 is preferably 0.2% or more, more preferably 0.5% or more, further preferably 0.7% or more, further preferably 1.0% or more, and particularly preferably 1.2% or more. In order to improve chemical durability, the content of P2O5 is 15% or less, preferably 10% or less, more preferably 5% or less, further preferably 3% or less, particularly preferably 2% or less, and most preferably 1.5% or less.

[0154] When MgO is contained in order to improve the melting property of glass, the content of MgO is preferably 0.1% or more, more preferably 0.3% or more, further preferably 0.5% or more, particularly preferably 0.75% or more, and most preferably 1% or more. From the viewpoint of improving ion exchange performance, the content of MgO is 10% or less, preferably 8% or less, more preferably 5% or less, further preferably 3% or less, particularly preferably 2% or less, and most preferably 1.5% or less.

[0155] When CaO is contained in order to improve the melting property of glass, the content of CaO is preferably 0.2% or more, more preferably 0.5% or more, further preferably 0.7% or more, and particularly preferably 1% or more. On the other hand, from the viewpoint of improving ion exchange performance, the content of CaO is 15% or less, preferably 5% or less, more preferably 2% or less, further preferably 1.5% or less, and particularly preferably 1.2% or less.

[0156] MgO, CaO and SrO, BaO or ZnO may be contained simultaneously, or SrO, BaO or ZnO may be contained instead of MgO and CaO. When SrO is contained, the content of SrO is preferably 0.1% or more, and more preferably 0.2% or more. On the other hand, in order to improve the ion exchange performance, the content of SrO is preferably 3% or less, more preferably 2% or less, further preferably 1.2% or less, further preferably 1% or less, and particularly preferably 0.5% or less. That is, when SrO is contained, the content of SrO is preferably 0.1% to 3%.

[0157] When ZnO is contained, the content of ZnO is preferably 0.1% or more, more preferably 0.2% or more. On the other hand, in order to improve the ion exchange performance, it is preferably 15% or less, more preferably 3% or less, further preferably 1% or less, and particularly preferably 0.5% or less.

[0158] When BaO is contained, the content of BaO is preferably 0.1% or more, more preferably 0.2% or more. On the other hand, in order to improve the ion exchange performance, the content of BaO is preferably 3% or less, more preferably 1% or less, and further preferably 0.5% or less. That is, when BaO is contained, the content of BaO is preferably 0.1% to 3%.

[0159] Alkaline earth metal oxides such as MgO, CaO, SrO, BaO and ZnO are components that improve the solubility of glass, but tend to reduce ion exchange performance. The total content of MgO, CaO, SrO, BaO and ZnO ([MgO] + [CaO] + [SrO] + [BaO] + [ZnO]) is preferably 0.5% to 15%. ([MgO] + [CaO] + [SrO] + [BaO] + [ZnO]) is preferably 15% or less, more preferably 10% or less, further preferably 5% or less, particularly preferably 3% or less, and even more particularly preferably 2.8% or less. In addition, the total content of MgO, CaO, SrO, BaO and ZnO ([MgO] + [CaO] + [SrO] + [BaO] + [ZnO]) is preferably 0.5% or more, more preferably 1% or more, and particularly preferably 1.5% or more.

[0160] Li2O is a component that forms surface compressive stress by ion exchange. When the content of Li2O is small, the strengthening characteristics (NaCS described later) become too low and the viscosity becomes too high. On the other hand, when the content of Li2O is too much, the strengthening characteristics (NaCS described later) become too high. From this point of view, the content of Li2O is more than 3%, preferably more than 5%, more preferably more than 7%, further preferably more than 7.5%, and particularly preferably more than 8%. In addition, the content of Li2O is less than 15%, preferably less than 12%, more preferably less than 10%, further preferably less than 9%, and particularly preferably less than 8.5%.

[0161] Na2O is a component that forms a surface compressive stress layer by ion exchange using a molten salt containing potassium, and is a component that improves the solubility of glass. When the content of Na2O is small, the viscosity becomes high and the strengthening characteristics (NaCS described later) become too high. On the other hand, when the content of Na2O is high, the strengthening characteristics (NaCS described later) become too low.

[0162] From this viewpoint, when containing Na2O, the content of Na2O is more than 2.5%, preferably more than 3%, more preferably more than 4%, further preferably more than 5%, particularly preferably more than 6%, and most preferably more than 7%. The content of Na2O is less than 15%, preferably less than 12%, more preferably less than 10%, further preferably less than 9%, particularly preferably less than 8.5%, and most preferably less than 8%.

[0163] K2O is a component that improves the solubility of glass and is also a component that makes the processability of glass good. The present glass preferably contains K2O. When the content of K2O is small, the viscosity becomes high and the devitrification characteristics deteriorate. On the other hand, when the content of K2O is high, the charging characteristics deteriorate. In the case of containing K2O, its content is preferably 0.05% or more, more preferably 0.1% or more, further preferably 0.15% or more, and particularly preferably 0.2% or more. In addition, the content of K2O is 5% or less, preferably 4% or less, more preferably 3% or less, further preferably 2% or less, and particularly preferably 1.5% or less.

[0164] ZrO2 is a component that increases the surface compressive stress generated by ion exchange, and ZrO2 may be contained. When ZrO2 is contained, the content of ZrO2 is preferably 0.005% or more, more preferably 0.2% or more, further preferably 1% or more, particularly preferably 1.2% or more, and more particularly preferably 1.3% or more. From the viewpoint of suppressing devitrification during melting, the content of ZrO2 is 5% or less, preferably 4% or less, more preferably 3% or less, further preferably 2% or less, and particularly preferably 1.7% or less.

[0165] Y2O3 is a component that suppresses breakage of chemically strengthened glass, and may be contained. When these components are contained, the content of Y2O3 is preferably 0.05% or more, more preferably 0.1% or more, and further preferably 0.15% or more.

[0166] From the viewpoint of preventing the glass from being easily devitrified during melting and preventing the quality of the chemically strengthened glass from being reduced, the content of Y2O3 is 5% or less, preferably 3% or less, more preferably 1% or less, further preferably 0.5% or less, and particularly preferably 0.2% or less.

[0167] La2O3 and Nb2O5 are components that inhibit the breakage of chemically strengthened glass, and La2O3 and Nb2O5 may be contained. When these components are contained, the content of each is preferably 0.1% or more, and more preferably 0.2% or more. In order to prevent the glass from losing clarity during melting and to prevent the quality of chemically strengthened glass, the content of La2O3 and Nb2O5 when contained is preferably 3% or less, more preferably 1% or less, and further preferably 0.3% or less.

[0168] TiO2 is a component that suppresses the scattering of fragments when chemically strengthened glass breaks, and TiO2 may be contained. When TiO2 is contained, the content of TiO2 is preferably 0.005% or more, more preferably 0.1% or more, further preferably 0.15% or more, and particularly preferably 0.2% or more. In order to suppress devitrification during melting, the content of TiO2 is preferably 5% or less, more preferably 2% or less, further preferably 1% or less, and particularly preferably 0.5% or less. TiO2 sometimes causes coloring, so in order to improve the transparency of the glass, it is further preferred that TiO2 is substantially not contained.

[0169] From the viewpoint of improving the strengthening characteristics (NaCS described later) and improving the charging characteristics, the ratio of the content of Li2O to the total content of Na2O and K2O [[Li2O] / ([Na2O]+[K2O])] is 0.5 or more, more preferably 0.7 or more, further preferably 0.85 or more, further preferably 0.95, further preferably 1.05 or more, further preferably 1.15 or more, and particularly preferably 1.25 or more. In addition, from the viewpoint of not making the strengthening characteristics (NaCS described later) too high and improving the devitrification characteristics, [Li2O] / ([Na2O]+[K2O]) is 3.5 or less, more preferably 3.0 or less, further preferably 2.5 or less, further preferably 2.0 or less, and particularly preferably 1.5 or less.

[0170] The ratio of the content of Li2O to the total content of Li2O, Na2O and K2O [[Li2O] / ([Li2O]+[Na2O]+[K2O])] is preferably 0.50 to 1.0. From the viewpoint of improving the strengthening characteristics (NaCS described later) and improving the charging characteristics, [Li2O] / ([Li2O]+[Na2O]+[K2O]) is preferably 0.50 or more, more preferably 0.55 or more, and further preferably 0.60 or more. In addition, from the viewpoint of preventing the strengthening characteristics (NaCS described later) from becoming too high and improving the devitrification characteristics, [Li2O] / ([Li2O]+[Na2O]+[K2O]) is preferably 1.0 or less, more preferably 0.75 or less, further preferably 0.70 or less, and further preferably 0.65 or less.

[0171] From the viewpoint of achieving both low viscosity and excellent strengthening characteristics, the total content of Al2O3 and Li2O ([Al2O3] + [Li2O]) is 27% or more, preferably 27.5% or more, more preferably 28.0% or more, further preferably 28.5% or more, further preferably 29.0% or more, and particularly preferably 29.5% or more. In addition, from the viewpoint of suppressing the viscosity from becoming high and suppressing the excessive introduction of compressive stress in the glass during chemical strengthening, [Al2O3] + [Li2O] is 35% or less, preferably 33% or less, more preferably 31% or less, further preferably 30.5% or less, and particularly preferably 30% or less.

[0172] The ratio of the content of Li2O to the total content of Al2O3 and Li2O ([Al2O3] + [Li2O]), [[Li2O] / ([Al2O3] + [Li2O])], is preferably 0.20 to 0.45. From the viewpoint of achieving both low viscosity and excellent strengthening properties, [Li2O] / ([Al2O3] + [Li2O]) is preferably 0.20 or more, more preferably 0.25 or more, and more preferably 0.28 or more. In addition, from the viewpoint of suppressing the decrease in devitrification viscosity and suppressing the excessive introduction of compressive stress in the glass during chemical strengthening, [Li2O] / ([Al2O3] + [Li2O]) is preferably 0.45 or less, more preferably 0.40 or less, and further preferably 0.35 or less.

[0173] The entropy function S value is a parameter related to chargeability and dielectric loss. The entropy function S value of the present tempered glass obtained by the following formula is preferably 0.25 or more, more preferably 0.28 or more, and further preferably 0.30 or more. In addition, the entropy function S value is preferably 0.40 or less, more preferably 0.35 or less, further preferably 0.33 or less, and particularly preferably 0.31 or less. When the entropy function S value is too large, the chargeability deteriorates, and when the entropy function S value is too small, the dielectric loss in the high frequency range increases.

[0174] S=-P Li ×log(P Li )-P Na ×log(P Na )-P K ×log(P K )

[0175] Here, P Li =[Li2O] / ([Li2O]+[Na2O]+[K2O])

[0176] P Na =[Na2O] / ([Li2O]+[Na2O]+[K2O])

[0177] PK =[K2O] / ([Li2O]+[Na2O]+[K2O])

[0178] Here, [Li2O], [Na2O], and [K2O] respectively represent the contents of Li2O, Na2O, and K2O in mol % based on oxides.

[0179] The total content of SiO2, B2O3 and P2O5 ([SiO2] + [B2O3] + [P2O5]) is preferably 50% to 69%. From the viewpoint of improving devitrification characteristics, [SiO2] + [B2O3] + [P2O5] is preferably 50% or more, more preferably 55% or more, further preferably 58% or more, further preferably 60% or more, and particularly preferably 61% or more. In addition, from the viewpoint of improving devitrification characteristics, [SiO2] + [B2O3] + [P2O5] is preferably 69% or less, more preferably 65% ​​or less, further preferably 64% or less, particularly preferably 63% or less, and even more preferably 62% or less.

[0180] Alkali metal oxides such as Na2O and K2O (hereinafter sometimes referred to as R2O) are components that lower the melting temperature of glass. It is preferred to contain alkali metal oxides such as Na2O and K2O, and the total content of Na2O and K2O ([Na2O] + [K2O]) is preferably 2.0% to 10%. From this point of view, [Na2O] + [K2O] is preferably 2.0% or more, more preferably 2.5% or more, and further preferably 3.0% or more. From the viewpoint of maintaining the strength of the glass, [Na2O] + [K2O] is preferably 10% or less, more preferably 8% or less, and further preferably 7% or less.

[0181] Alkali metal oxides such as Li2O, Na2O and K2O (hereinafter sometimes referred to as R2O) are components that lower the melting temperature of the glass. It is preferred that alkali metal oxides such as Li2O, Na2O and K2O are contained, and the total content of Li2O, Na2O and K2O ([Li2O] + [Na2O] + [K2O]) is preferably 12% to 20%. From this point of view, [Li2O] + [Na2O] + [K2O] is preferably 12% or more, more preferably 14% or more, further preferably 15.0% or more, particularly preferably 15.5% or more, and even more preferably 16.0% or more. From the viewpoint of maintaining the strength of the glass, [Li2O] + [Na2O] + [K2O] is preferably 20% or less, more preferably 18% or less, further preferably 17% or less, and particularly preferably 16.5% or less.

[0182] The total content of Al2O3 and B2O3 ([Al2O3] + [B2O3]) is preferably 19% to 40%. From the viewpoint of improving fracture toughness, [Al2O3] + [B2O3] is preferably 19% or more, more preferably 22% or more, further preferably 23% or more, and particularly preferably 24% or more. In addition, from the viewpoint of improving acid resistance, [Al2O3] + [B2O3] is preferably 40% or less, more preferably 30% or less, further preferably 27% or less, and particularly preferably 25% or less. When the acid resistance is low, problems such as difficulty in pickling occur during glass processing.

[0183] The total content of B2O3 and P2O5 ([B2O3] + [P2O5]) is preferably 2% to 10%. From the viewpoint of reducing viscosity while maintaining the devitrification characteristics, [B2O3] + [P2O5] is preferably 2% or more, more preferably 3% or more, further preferably 4% or more, and particularly preferably 5% or more. In addition, from the viewpoint of improving acid resistance, [B2O3] + [P2O5] is preferably 10% or less, more preferably 8% or less, further preferably 7% or less, and particularly preferably 6% or less.

[0184] When FeO is contained, the content is preferably 200 ppm or less in terms of mass % based on oxides. If it exceeds 200 ppm, coloration may occur, and the color tone of the display may change.

[0185] As a clarifier, trace amounts (preferably 1% by mass or less) of Cl, Sn, and S may be contained.

[0186] From the viewpoint of improving chemical resistance, the total content of Sc2O3, Ga2O3, GeO2, Nb2O5, In2O3, TeO2, HfO2, Ta2O5, WO3, Bi2O3, La2O3, Gd2O3, Yb2O3, etc. may be contained, preferably in a total content of 0.01% to 1.0% by mass. 3Zn At least one of the group consisting of Lu2O3.

[0187] The β-OH value is related to the viscosity and bubbles of the glass. The β-OH value is preferably 0.05 to 0.5. When the β-OH value is too low, it is difficult to obtain the effect of reducing the viscosity. When the β-OH value is too high, bubbles are generated due to decomposition, and sometimes the bubble quality of the glass is poor.

[0188] In order to suppress the breakage of chemically strengthened glass, Ta2O5 and Gd2O3 may be contained in small amounts. However, since the refractive index and reflectivity increase, their contents are preferably 1% or less, more preferably 0.5% or less, and further preferably substantially not contained.

[0189] When coloring glass, coloring components can be added within a range that does not hinder the realization of the desired chemical strengthening characteristics. Examples of coloring components include Co3O4, MnO2, Fe2O3, NiO, CuO, Cr2O3, V2O5, Bi2O3, SeO2, CeO2, Er2O3, and Nd2O3. These can be used alone or in combination.

[0190] From the viewpoint of suppressing the devitrification of the glass, the total content of the coloring components is preferably 5% or less, more preferably 3% or less, and further preferably 1% or less. In the case of increasing the visible light transmittance of the glass, it is preferred that these components are substantially not contained.

[0191] In addition, as a clarifier for melting glass, SO3, chloride, fluoride, etc. may be appropriately contained. Preferably, As2O3 is substantially free of content. When Sb2O3 is contained, it is preferably 0.3% by mass or less, more preferably 0.1% by mass or less, and most preferably substantially free of content.

[0192] (characteristic)

[0193] The present tempering glass preferably satisfies the following (A1) to (A4).

[0194] (A1) Young's modulus is 80 GPa to 100 GPa.

[0195] (A2) In the case of a plate having a thickness of 0.7 mm, the surface compressive stress CS0 when ion exchange is performed in 100 mass % sodium nitrate salt at 380° C. for 4 hours is 200 MPa to 450 MPa, and the depth of the compressive stress layer is 70 μm to 120 μm.

[0196] (A3) Viscosity reaches 10 2 dPa·s when the temperature (T2) is below 1650°C and the viscosity reaches 10 4 dPa·s is 1250°C or less.

[0197] (A4) Fracture toughness value K IC 0.75MPa·m 1 / 2 ~0.85MPa·m 1 / 2 .

[0198] Each item is described below.

[0199] The higher the Young's modulus, the higher the fracture toughness and the higher the CT limit. From this viewpoint, the Young's modulus of this strengthening glass is preferably more than 77GPa, more preferably more than 80GPa, and more preferably more than 85GPa. On the other hand, when the Young's modulus is too high, the diffusion of ions is slow during chemical strengthening, and there is a tendency to be difficult to obtain deep DOC. Therefore, the Young's modulus is preferably less than 100GPa, more preferably less than 95GPa, and more preferably less than 90GPa. Young's modulus can be measured, for example, by ultrasonic pulse method.

[0200] When the tempered glass is in the form of a plate having a thickness of 0.7 mm, the surface compressive stress (hereinafter also referred to as NaCS) when ion exchange is carried out in 100 mass % sodium nitrate salt at 380° C. for 4 hours is preferably 200 MPa to 450 MPa, and the depth of the compressive stress layer (hereinafter also referred to as NaDOL) is preferably 70 μm to 120 μm.

[0201] NaCS is preferably 200 MPa or more, more preferably 250 MPa or more, further preferably 300 MPa or more, and particularly preferably 350 MPa or more. By having NaCS of 250 MPa or more, sufficient compressive stress can be imparted to a deep region with a depth of 50 μm or more. In addition, NaCS is preferably 450 MPa or less, more preferably 425 MPa or less, further preferably 400 MPa or less, and particularly preferably 375 MPa or less. When NaCS is greater than 450 MPa, the DOC has to be shallower due to the limitation of the CT limit during stress distribution design. As a result, the compressive stress (CS) in a deep region with a depth of 50 μm or more is reduced. 50 , CS 90 ) becomes smaller.

[0202] NaDOL is preferably 70 μm or more, more preferably 80 μm or more, further preferably 90 μm or more, and particularly preferably 100 μm or more. By having NaDOL of 70 μm or more, chemical strengthening can be performed in a short time, so the process efficiency becomes better. NaDOL is preferably 150 μm or less, more preferably 140 μm or less, further preferably 130 μm or less, and particularly preferably 120 μm or less. By having NaDOL of 150 μm or less, it is possible to ensure a chemical strengthening time sufficient to stably control the chemical strengthening process. When the chemical strengthening time becomes too short, the influence of the diffusion of ions in the preheating before and after immersion in the strengthening salt and the process of removing the molten strengthening salt becomes relatively large, and the deviation of the strengthening stress distribution of mass production becomes large.

[0203] From the viewpoint of reducing viscosity, improving productivity and SDGs, the temperature (T2) at which the viscosity logη of the tempered glass reaches 2 (poise) is preferably 1650°C or lower, more preferably 1615°C or lower, and further preferably 1590°C or lower. T2 is usually 1400°C or higher. The temperature (T2) at which the viscosity logη reaches 2 (poise) is similar to the temperature at which the viscosity reaches 10 2 The temperature (T2) at dPa·s has the same meaning.

[0204] From the viewpoint of reducing viscosity, improving productivity and SDGs, the temperature (T4) at which the viscosity logη of the tempered glass reaches 4 (poise) is preferably 1250°C or lower, more preferably 1220°C or lower, and further preferably 1200°C or lower. T4 is usually 1000°C or higher. The temperature at which the viscosity logη reaches 4 (poise) is similar to the temperature at which the viscosity reaches 10 4 The temperature at dPa·s (T4) has the same meaning.

[0205] The fracture toughness value (K Ic ) is preferably 0.75 MPa·m 1 / 2 More preferably, 0.77 MPa·m 1 / 2 More preferably, 0.80 MPa·m 1 / 2 Above, particularly preferably 0.82 MPa·m 1 / 2 When the fracture toughness value (K Ic ) is 0.75MPa·m 1 / 2 When K is above 0.05, the number of broken pieces of glass can be effectively suppressed. Ic When K increases, the Young's modulus increases, and the strength against bending tends to decrease. From the perspective of ensuring sufficient bending strength, K Ic Preferably 0.85 MPa·m 1 / 2 Below, more preferably 0.84 MPa·m 1 / 2 Below, more preferably 0.83 MPa·m 1 / 2 the following.

[0206] It should be noted that the fracture toughness value (K Ic ) means that K is measured by the DCDC method described in detail in the examples described later. I -v curve to obtain the fracture toughness value.

[0207] In order to suppress stress relaxation during chemical strengthening, the glass transition temperature (Tg) of the present strengthening glass is preferably 480° C. or higher. In order to suppress stress relaxation and obtain a large compressive stress, Tg is more preferably 500° C. or higher, and further preferably 520° C. or higher.

[0208] In order to increase the ion diffusion rate during chemical strengthening, Tg is preferably 700° C. or lower. In order to easily obtain a deep DOC, Tg is more preferably 650° C. or lower, and further preferably 600° C. or lower.

[0209] The glass transition temperature Tg was measured based on JIS R1618:2002 using a thermal dilatometer (manufactured by Bruker AXS; TD5000SA) at a heating rate of 10°C / min to obtain a thermal expansion curve [unit: °C].

[0210] For the present tempered glass, from the viewpoint of suppressing the precipitation of crystals during bending, the crystallization peak temperature of the chemically tempered glass measured by the following measurement method is preferably higher than the softening point of the glass. From this viewpoint, the value obtained by subtracting Tg from the crystallization peak temperature (hereinafter, also referred to as DSC peak temperature) (DSC peak temperature-Tg) is preferably 180°C or higher, more preferably 220°C or higher, and even more preferably 250°C or higher. In addition, it is more preferred that no crystallization peak is observed.

[0211] (Measurement method)

[0212] About 70 mg of glass was pulverized and ground with an agate mortar, and the temperature was measured from room temperature to 1000° C. using a differential scanning calorimeter (DSC) at a heating rate of 10° C. / min.

[0213] From the viewpoint of improving productivity, the specific gravity of the tempered glass is preferably 2.35 or more, more preferably 2.38 or more, and further preferably 2.40 or more. In addition, the specific gravity is preferably 2.45 or less, more preferably 2.43 or less, and further preferably 2.41 or less. The specific gravity is measured by the Archimedean method.

[0214] The shape of the tempered glass is not particularly limited, and may have a curved surface. As the curved surface shape, there may be a shape having an R portion on one surface and a flat surface opposite to the surface (sometimes referred to as a 2.5D shape) or a 3D shape having an R shape. In this specification, a "2.5D shape" refers to a shape having an R portion at the corner of a flat plate (2D). In this specification, a "3D shape" refers to a glass having a curved shape that is not a flat plate (2D).

[0215] From the viewpoint of effective chemical strengthening treatment and the viewpoint of weight when used as a protective glass, the thickness of the present strengthening glass is usually preferably 1.5 mm or less, more preferably 1.2 mm or less, further preferably 1.1 mm or less, particularly preferably 1.0 mm or less, and most preferably 0.8 mm or less. From the viewpoint of strength, it is preferably 0.4 mm or more, more preferably 0.45 mm or more, further preferably 0.50 mm or more, and particularly preferably 0.55 mm or more.

[0216] (Manufacturing method)

[0217] The tempered glass can be manufactured by a conventional method. For example, the raw materials of each component of the glass are mixed and heated and melted in a glass melting furnace. Then, the glass is homogenized by a known method, formed into a desired shape such as a glass plate, and slowly cooled.

[0218] As the forming method of the glass sheet, for example, there can be mentioned: float process, press process, fusion process and down-draw process. The float process suitable for mass production is particularly preferred. In addition, continuous forming methods other than the float process, namely, fusion process and down-draw process are also preferred.

[0219] Then, the formed glass is ground and polished as needed to form a glass substrate. It should be noted that when the glass substrate is cut into a specified shape and size or the glass substrate is chamfered, if the cutting and chamfering of the glass substrate are performed before the chemical strengthening treatment described later, a compressive stress layer is also formed on the end surface by the subsequent chemical strengthening treatment, which is preferred.

[0220] (Third Method)

[0221] <Li2O-Al2O3-SiO2 chemically strengthened glass>

[0222] The third formula Li2O-Al2O3-SiO2 type chemically strengthened glass (hereinafter sometimes referred to as the present Li2O-Al2O3-SiO2 type chemically strengthened glass) contains 2% or more of B2O3, in terms of mol% based on oxides. The third formula Li2O-Al2O3-SiO2 type chemically strengthened glass has a Young's modulus greater than 76 GPa, a surface compressive stress CS0 of 200 MPa to 450 MPa and a compressive stress layer depth DOC of 70 μm to 120 μm when chemically strengthened in 100 mass % of sodium nitrate salt at 380°C for 4 hours, and a viscosity of 10 2 The temperature (T2) at dPa·s is 1650°C or less.

[0223] From the viewpoint of improving scratch resistance, the content of B2O3 in the present Li2O-Al2O3-SiO2-based chemically strengthened glass is 2% or more, preferably 3% or more, more preferably 4% or more, further preferably 5% or more, and particularly preferably 6% or more. Since B2O3 is a component that easily causes stress relaxation after chemical strengthening, from the viewpoint of preventing the reduction of surface compressive stress caused by stress relaxation, the content of B2O3 is preferably 10% or less, more preferably 9% or less, further preferably 8% or less, and particularly preferably 7% or less.

[0224] The Young's modulus of the present Li2O-Al2O3-SiO2-based chemically strengthened glass is greater than 76 GPa, preferably 77 GPa or more, more preferably 80 GPa or more, and further preferably 85 GPa or more. On the other hand, when the Young's modulus is too high, the diffusion of ions is slow during chemical strengthening, and it is difficult to obtain a deep DOC. Therefore, the Young's modulus is preferably 100 GPa or less, more preferably 95 GPa or less, and further preferably 90 GPa or less.

[0225] The NaCS of the present Li2O-Al2O3-SiO2-based chemically strengthened glass is 200MPa or more, preferably 250MPa or more, more preferably 300MPa or more, and particularly preferably 350MPa or more. By having NaCS of 200MPa or more, sufficient compressive stress can be imparted to deep regions with a depth of 50μm or more. In addition, NaCS is 450MPa or less, preferably 400MPa or less, more preferably 350MPa or less, and particularly preferably 300MPa or less. When NaCS is greater than 450MPa, the DOC has to be shallower due to the limitation of the CT limit during stress distribution design, and as a result, the compressive stress in deep regions with a depth of 50μm or more becomes smaller.

[0226] The NaDOL of the present Li2O-Al2O3-SiO2-based chemically strengthened glass is 70 μm or more, preferably 80 μm or more, more preferably 90 μm or more, and particularly preferably 100 μm or more. By having a NaDOL of 70 μm or more, chemical strengthening can be performed in a short time, and the process cost is reduced. The NaDOL is 120 μm or less, preferably 110 μm or less, more preferably 100 μm or less, and particularly preferably 90 μm or less. By having a NaDOL of 120 μm or less, a chemical strengthening time sufficient to stably manage the chemical strengthening process can be ensured.

[0227] From the perspective of improving productivity, the viscosity of the Li2O-Al2O3-SiO2-based chemically strengthened glass reaches 10 2The temperature (T2) at dPa·s is 1650° C. or lower, preferably 1615° C. or lower, and more preferably 1590° C. or lower. T2 is usually 1400° C. or higher.

[0228] Regarding the composition, characteristics and manufacturing method of the Li2O-Al2O3-SiO2 type chemically strengthened glass other than those described above, the composition, characteristics and manufacturing method described above regarding the (composition), (characteristics) and (manufacturing method) of the chemically strengthened glass can be appropriately adopted.

[0229] (Second method)

[0230] <Glass>

[0231] The glass of the second embodiment contains, in terms of mol% based on oxides:

[0232] 50%~65% SiO2,

[0233] 15% to 25% Al2O3,

[0234] 2% to 10% B2O3,

[0235] 0%~15% P2O5,

[0236] 0%~15% ZnO,

[0237] 0%~10%MgO,

[0238] 0%~15%CaO,

[0239] 3% to 15% Li2O,

[0240] 2.5% to 15% Na2O,

[0241] 0%~5% K2O,

[0242] 0%~5% ZrO2,

[0243] 0% to 5% Y2O3, and

[0244] 0%~5% TiO2,

[0245] [Li2O] / ([Na2O]+[K2O]) is 0.5 to 3.5,

[0246] [Al2O3]+[Li2O] is 27% to 35%,

[0247] The entropy function S value of the alkali ion represented by the following formula is 0.25 to 0.40.

[0248] S=-P Li ×log(P Li)-P Na ×log(P Na )-P K ×log(P K )

[0249] P Li =[Li2O] / ([Li2O]+[Na2O]+[K2O])

[0250] P Na =[Na2O] / ([Li2O]+[Na2O]+[K2O])

[0251] P K =[K2O] / ([Li2O]+[Na2O]+[K2O])

[0252] In the formula, [ ] represents the content of each component in parentheses in terms of mol % based on oxides.

[0253] The entropy function S value of the glass of the second embodiment obtained by the following formula is 0.25 or more, preferably 0.28 or more, and more preferably 0.30 or more. In addition, from the viewpoint of suppressing excessive introduction of compressive stress into the glass during chemical strengthening, the entropy function S value is 0.40 or less, preferably 0.35 or less, more preferably 0.33 or less, and particularly preferably 0.31 or less.

[0254] S=-P Li ×log(P Li )-P Na ×log(P Na )-P K ×log(P K ),

[0255] Here, P Li =[Li2O] / ([Li2O]+[Na2O]+[K2O])

[0256] P Na =[Na2O] / ([Li2O]+[Na2O]+[K2O])

[0257] P K =[K2O] / ([Li2O]+[Na2O]+[K2O])

[0258] Here, [Li2O], [Na2O], and [K2O] represent the contents of Li2O, Na2O, and K2O in mol% based on oxides, respectively. When the entropy function S value is too large, the charging characteristics deteriorate, and when the entropy function S is too small, the dielectric loss in the high frequency range increases.

[0259] The glass satisfying the second aspect of the composition can easily form a preferred stress distribution by chemical strengthening treatment, does not exceed the CT limit, and can ensure drop strength, so it is preferably used as chemically strengthened glass. The present glass is strengthened by, for example, an ion exchange method.

[0260] Regarding the composition, characteristics and manufacturing method of the glass of the second embodiment other than those described above, the composition, characteristics and manufacturing method described above regarding the (composition), (characteristics) and (manufacturing method) of the chemically strengthened glass of the first embodiment can be appropriately adopted.

[0261] (Fourth Method)

[0262] <Chemically strengthened glass>

[0263] The chemically strengthened glass of the fourth aspect contains, in terms of mol% based on oxides:

[0264] 50%~67% SiO2,

[0265] 16% to 25% Al2O3,

[0266] 2% to 10% B2O3,

[0267] 0%~15% P2O5,

[0268] 0%~15% ZnO,

[0269] 0%~10%MgO,

[0270] 0%~15%CaO,

[0271] 3% to 15% Li2O,

[0272] 2.5% to 15% Na2O,

[0273] 0%~5% K2O,

[0274] 0%~5% ZrO2,

[0275] 0% to 5% Y2O3, and

[0276] 0%~5% TiO2,

[0277] [Li2O] / ([Na2O]+[K2O]) is 0.5 to 3.5,

[0278] [Al2O3]+[Li2O] is 22% to 35%,

[0279] The Young's modulus of the chemically strengthened glass is 77 GPa or more.

[0280] In the formula, [ ] represents the content of each component described in parentheses in terms of mol % based on oxides.

[0281] In the fourth embodiment of the chemically strengthened glass, in order to improve chemical durability, the content of SiO2 is 50% or more, preferably 52% or more, more preferably 54% or more, further preferably 55% or more, and particularly preferably 56% or more. In order to make the meltability of the glass good, the content of SiO2 is 67% or less, preferably 66% or less, more preferably 65% ​​or less, further preferably 62% or less, further preferably 60% or less, particularly preferably 59% or less, and most preferably 58% or less.

[0282] In the fourth embodiment of the chemically strengthened glass, in order to improve the ion exchangeability during chemical strengthening, increase the surface compressive stress after strengthening, or increase the glass transition temperature (Tg) and Young's modulus, the content of Al2O3 is 16% or more, preferably 17% or more, more preferably 19% or more, further preferably 20% or more, and particularly preferably 20.5% or more. The content of Al2O3 is 25% or less, preferably 23% or less, more preferably 22% or less, and further preferably 21.5% or less.

[0283] In the fourth embodiment of the chemically strengthened glass, from the viewpoint of achieving both low viscosity and excellent strengthening characteristics, the total content of Al2O3 and Li2O ([Al2O3] + [Li2O]) is 22% or more, preferably 22.5% or more, more preferably 23% or more, further preferably 23.5% or more, more preferably 24% or more, further preferably 25% or more, further preferably 27% or more, and particularly preferably 29% or more. In addition, from the viewpoint of suppressing the viscosity from becoming high and suppressing the excessive introduction of compressive stress in the glass during chemical strengthening, [Al2O3] + [Li2O] is 35% or less, preferably 33% or less, more preferably 31% or less, further preferably 30.5% or less, and particularly preferably 30% or less.

[0284] In the fourth embodiment of the chemically strengthened glass, from the viewpoint of improving fracture toughness and CT limit, the Young's modulus is 77 GPa or more, preferably 78 GPa or more, and more preferably 80 GPa or more. In addition, the Young's modulus is preferably 100 GPa or less, more preferably 95 GPa or less, and further preferably 90 GPa or less.

[0285] Regarding the composition, characteristics, and manufacturing method of the chemically strengthened glass of the fourth embodiment other than those described above, the composition, characteristics, and manufacturing method described above regarding the (composition), (characteristics), and (manufacturing method) of the chemically strengthened glass of the first embodiment can be appropriately adopted.

[0286] (Fifth Method)

[0287] <Glass>

[0288] The glass of the fifth embodiment contains, in terms of mol% based on oxides:

[0289] 50%~67% SiO2,

[0290] 16% to 25% Al2O3,

[0291] 2% to 10% B2O3,

[0292] 0%~15% P2O5,

[0293] 0%~15% ZnO,

[0294] 0%~10%MgO,

[0295] 0%~15%CaO,

[0296] 3% to 15% Li2O,

[0297] 2.5% to 15% Na2O,

[0298] 0%~5% K2O,

[0299] 0%~5% ZrO2,

[0300] 0% to 5% Y2O3, and

[0301] 0%~5% TiO2,

[0302] [Li2O] / ([Na2O]+[K2O]) is 0.5 to 3.5,

[0303] [Al2O3]+[Li2O] is 22% to 35%,

[0304] The Young's modulus of the glass is 77 GPa or more,

[0305] The entropy function S value of the alkali ion represented by the following formula is 0.25 to 0.40.

[0306] S=-P Li ×log(P Li )-P Na ×log(P Na )-P K ×log(P K )

[0307] P Li =[Li2O] / ([Li2O]+[Na2O]+[K2O])

[0308] PNa =[Na2O] / ([Li2O]+[Na2O]+[K2O])

[0309] P K =[K2O] / ([Li2O]+[Na2O]+[K2O])

[0310] In the formula, [ ] represents the content of each component in parentheses in terms of mol % based on oxides.

[0311] In the glass of the fifth embodiment, in order to improve chemical durability, the content of SiO2 is 50% or more, preferably 52% or more, more preferably 54% or more, further preferably 55% or more, and particularly preferably 56% or more. In order to make the melting property of the glass good, the content of SiO2 is 67% or less, preferably 66% or less, more preferably 65% ​​or less, further preferably 62% or less, further preferably 60% or less, particularly preferably 59% or less, and most preferably 58% or less.

[0312] In the glass of the fifth embodiment, in order to improve the ion exchangeability during chemical strengthening, increase the surface compressive stress after strengthening, or to increase the glass transition temperature (Tg) and Young's modulus, the content of Al2O3 is 16% or more, preferably 17% or more, more preferably 19% or more, further preferably 20% or more, and particularly preferably 20.5% or more. The content of Al2O3 is 25% or less, preferably 23% or less, more preferably 22% or less, and further preferably 21.5% or less.

[0313] In the fifth embodiment of the glass, from the viewpoint of taking both low viscosity and excellent strengthening characteristics into consideration, the total content of Al2O3 and Li2O ([Al2O3] + [Li2O]) is 22% or more, preferably 22.5% or more, more preferably 23% or more, further preferably 23.5% or more, more preferably 24% or more, further preferably 25% or more, further preferably 27% or more, and particularly preferably 29% or more. In addition, from the viewpoint of suppressing the viscosity from becoming high and suppressing the excessive introduction of compressive stress in the glass during chemical strengthening, [Al2O3] + [Li2O] is 35% or less, preferably 33% or less, more preferably 31% or less, further preferably 30.5% or less, and particularly preferably 30% or less.

[0314] In the fifth embodiment of the glass, from the viewpoint of improving fracture toughness and CT limit, Young's modulus is 77 GPa or more, preferably 78 GPa or more, more preferably 80 GPa or more. In addition, Young's modulus is preferably 100 GPa or less, more preferably 95 GPa or less, and further preferably 90 GPa or less.

[0315] Regarding the composition, properties and manufacturing method of the glass of the fifth embodiment other than those described above, the composition, properties and manufacturing method described above regarding the (composition), (properties) and (manufacturing method) of the chemically strengthened glass in the first embodiment can be appropriately adopted.

[0316] (Sixth Method)

[0317] <Chemically strengthened glass>

[0318] The chemically strengthened glass of the present invention (hereinafter sometimes referred to as the present chemically strengthened glass) can be produced by chemically strengthening the above-mentioned chemically strengthened glass, Li2O-Al2O3-SiO2-based chemically strengthened glass or glass to form a compressive stress layer.

[0319] (Stress characteristics)

[0320] The chemically strengthened glass preferably has the following stress characteristics (C1) to (C6).

[0321] (C1) The surface compressive stress CS0 is 500 MPa or more.

[0322] (C2) When the plate thickness is t (μm) and the depth of the compressive stress layer is DOC (μm), DOC / t is 0.125 to 0.225.

[0323] (C3) In the stress distribution with compressive stress (MPa) on the vertical axis and depth (μm) from the surface on the horizontal axis, the average slope in the region of 1 μm to 3 μm from the surface is greater than -400 and less than -100.

[0324] (C4) In the stress distribution with compressive stress (MPa) on the vertical axis and depth (μm) from the surface on the horizontal axis, the average slope in the region from a depth of 20 μm from the surface to a depth of the compressive stress layer DOC / 2 μm is greater than -4 and less than -1.5.

[0325] (C5) When the plate thickness is t (μm), the compressive stress value CS at a depth of 50 μm from the surface is 50 It is above 0.1t(MPa).

[0326] (C6) When the plate thickness is t (μm), the compressive stress value CS at a depth of 90 μm from the surface is 90 It is above 0.03t(MPa).

[0327] Each item is described below.

[0328] From the viewpoint of suppressing cracking caused by deformation such as bending, the surface compressive stress CS0 of the chemically strengthened glass is preferably 500 MPa or more, more preferably 550 MPa or more, further preferably 650 MPa or more, and particularly preferably 750 MPa or more. The larger the CS0, the higher the strength, but when the CS0 is too large, severe crushing may occur in the case of cracking, so it is preferably 1400 MPa or less, more preferably 1200 MPa or less.

[0329] When the plate thickness is t (μm) and the depth of the compressive stress layer is DOC (μm), from the viewpoint of being difficult to break even when damage occurs on the surface, DOC / t of the chemically strengthened glass is preferably 0.125 or more, more preferably 0.14 or more, and further preferably 0.16 or more. In addition, since tensile stress is generated inside in accordance with the compressive stress formed near the surface, from the viewpoint of suppressing the scattering of fragments when the chemically strengthened glass breaks, DOC / t is preferably 0.225 or less, more preferably 0.20 or less, and further preferably 0.18 or less.

[0330] In the stress distribution with the vertical axis being the compressive stress (MPa) and the horizontal axis being the depth (μm) from the surface, the average slope in the region of 1 μm to 3 μm from the surface of the chemically strengthened glass is preferably greater than -400, more preferably greater than -300, and further preferably greater than -200. By having an average slope greater than -400 in the region of 1 μm to 3 μm from the surface, a sufficiently high surface CS can be ensured. The average slope in the region of 1 μm to 3 μm from the surface is preferably less than -100, more preferably less than -150, and further preferably less than -200. By having an average slope less than -100 in the region of 1 μm to 3 μm from the surface, the reduction in bending strength due to shallow damage generated during glass processing can be suppressed. In this specification, "average slope" refers to the average value obtained by finding the slope of the stress distribution per 1 μm within the range of the depth for which the slope is found.

[0331] In the stress distribution with the vertical axis representing compressive stress (MPa) and the horizontal axis representing depth (μm) from the surface, the average slope in the region from the depth of 20 μm from the surface to the depth of the compressive stress layer DOC / 2 μm of the present chemically strengthened glass is preferably greater than -4, more preferably greater than -3.5, and even more preferably greater than -3.0. By having the average slope greater than -4, a high CS 50 , when the average slope is less than -4, it is difficult to achieve high CS 90 In addition, the average slope is preferably less than -1.5, more preferably less than -2.0, and further preferably less than -2.5. By having the average slope less than -1.5, a high CS 90, but when the average slope is greater than -1.5, it is difficult to achieve a high CS 50 .

[0332] When the plate thickness is t (μm), the compressive stress value CS of the chemically strengthened glass at a depth of 50 μm from the surface is 50 It is preferably 0.1t (MPa) or more, more preferably 0.13t (MPa) or more, further preferably 0.15t (MPa) or more, and particularly preferably 0.17t (MPa) or more. 50 When the tensile strength is 0.1 t (MPa) or more, it is easy to prevent the chemically strengthened glass from breaking when a portable terminal or the like having the chemically strengthened glass as a protective glass is dropped. 50 The larger the value, the higher the intensity. However, when CS 50 When it is too large, it may cause severe breakage in the event of rupture, so CS 50 It is preferably 0.3 t (MPa) or less, and more preferably 0.25 t (MPa) or less.

[0333] When the plate thickness is t (μm), the compressive stress value CS of the chemically strengthened glass at a depth of 90 μm from the surface is 90 It is preferably 0.03t (MPa) or more, more preferably 0.04t (MPa) or more, further preferably 0.05t (MPa) or more, and particularly preferably 0.07t (MPa) or more. 90 When the tensile strength is 0.03 t (MPa) or more, it is easy to prevent the chemically strengthened glass from breaking when a portable terminal or the like having the chemically strengthened glass as a cover glass falls onto coarse sand or the like. 90 The larger the value, the higher the intensity. 90 If it is too large, severe breakage may occur in the event of rupture, so CS 90 It is preferably 0.15 t (MPa) or less, more preferably 0.14 t (MPa) or less, further preferably 0.13 t (MPa) or less, and particularly preferably 0.10 t (MPa) or less.

[0334] (Chemical strengthening treatment)

[0335] Chemical strengthening treatment is a treatment in which the glass is brought into contact with the metal salt by immersing the glass in a melt of a metal salt (e.g., potassium nitrate) containing metal ions with a large ionic radius (typically Na ions or Li ions), thereby replacing the metal ions with a small ionic radius (typically Na ions or K ions) in the glass with metal ions with a large ionic radius (typically Na ions or K ions relative to Li ions, and K ions relative to Na ions).

[0336] In order to speed up the chemical strengthening treatment, it is preferred to use "Li-Na exchange" in which Li ions in the glass are exchanged with Na ions. In addition, in order to form a large compressive stress by ion exchange, it is preferred to use "Na-K exchange" in which Na ions in the glass are exchanged with K ions.

[0337] As molten salts for chemical strengthening treatment, for example, nitrates, sulfates, carbonates, chlorides, etc. can be cited. Among them, as nitrates, for example, lithium nitrate, sodium nitrate, potassium nitrate, cesium nitrate, silver nitrate, etc. can be cited. As sulfates, for example, lithium sulfate, sodium sulfate, potassium sulfate, cesium sulfate, silver sulfate, etc. can be cited. As carbonates, for example, lithium carbonate, sodium carbonate, potassium carbonate, etc. can be cited. As chlorides, for example, lithium chloride, sodium chloride, potassium chloride, cesium chloride, silver chloride, etc. can be cited. These molten salts can be used alone or in combination.

[0338] The treatment conditions of the chemical strengthening treatment can be selected in consideration of the glass composition, the type of molten salt, etc., and the time and temperature can be selected. For example, the chemical strengthening treatment of the chemically strengthened glass can be preferably performed at 450° C. or less for preferably 1 hour or less. Specifically, for example, a treatment of immersing in a molten salt (e.g., a mixed salt of lithium nitrate and sodium nitrate) containing 0.3% by mass of Li and 99.7% by mass of Na at preferably 450° C. for preferably about 0.5 hours can be cited.

[0339] The chemical strengthening treatment can be performed by two or more steps of ion exchange. Specifically, the two-step ion exchange is performed as follows. First, the chemically strengthened glass is immersed in a metal salt containing Na ions (e.g., sodium nitrate) preferably at about 350° C. to about 500° C. for preferably about 0.1 hour to about 10 hours. As a result, ion exchange of Li ions in the chemically strengthened glass with Na ions in the metal salt occurs, thereby forming a relatively deep compressive stress layer.

[0340] When a compressive stress layer is formed on the surface of a glass article by chemical strengthening treatment, a tensile stress corresponding to the total amount of compressive stress on the surface will inevitably be generated in the center of the glass article. When the tensile stress value becomes too large, the glass article breaks violently and fragments fly. When CT exceeds its threshold value (hereinafter, also referred to as CT limit), the number of breakages during damage increases explosively. In the case of more than two steps of ion exchange, the maximum tensile stress value of the stress distribution formed inside the glass by the initial ion exchange (first ion exchange) is preferably greater than the CT limit. The maximum tensile stress value after the first ion exchange is greater than the CT limit, and compressive stress is sufficiently introduced by the first ion exchange. In the subsequent second ion exchange process, after the stress value of the surface layer of the glass is reduced, a high CS can be maintained. 50 and CS 90 .

[0341] Next, the substrate is immersed in a metal salt containing K ions (e.g., potassium nitrate) preferably at about 350°C to about 500°C for about 0.1 hour to about 10 hours. As a result, a large compressive stress is generated in the portion of the compressive stress layer formed in the previous treatment, for example, within a depth of about 10 μm. According to such a two-step treatment, a stress distribution with a large surface compressive stress value is easily obtained.

[0342] The ion distribution and stress characteristics in the chemically strengthened glass can be adjusted according to the basic composition of the chemically strengthened glass and the conditions of the chemical strengthening treatment. Here, the "basic composition of the chemically strengthened glass" refers to the composition of the glass before chemical strengthening. Except for the case where an extreme ion exchange treatment is performed, the composition of the chemically strengthened glass as a whole has a composition similar to that of the glass before strengthening, and usually, the composition of the glass before strengthening is the same as the composition of the center of the plate thickness in the chemically strengthened glass. In particular, except for the case where an extreme ion exchange treatment is performed, the composition of the deepest part from the glass surface is the same as the composition of the glass before strengthening.

[0343] (Applications of chemically strengthened glass)

[0344] The chemically strengthened glass of the present invention is particularly useful as a protective glass used in electronic devices such as mobile phones and smart phones. In addition, it is useful for protective glass of electronic devices such as televisions, personal computers, touch panels, etc. that are not intended to be carried, walls of elevators, walls of buildings such as houses and buildings (full-screen displays). In addition, it is also useful for building materials such as window glass, desktops, interiors of cars or airplanes, their protective glasses, and housings with curved shapes.

[0345] (Uses of glass)

[0346] The glass of the present invention is particularly useful as a protective glass used in electronic devices such as mobile phones and smart phones. In addition, it is useful for protective glass of electronic devices such as televisions, personal computers, touch panels, etc. that are not intended to be carried, walls of elevators, walls of buildings such as houses and buildings (full-screen displays). In addition, it is also useful for building materials such as window glass, desktops, interiors of cars or airplanes, their protective glasses, and housings with curved shapes.

[0347] Example

[0348] Hereinafter, the present invention will be described by way of examples, but the present invention is not limited thereto.

[0349] (Production of chemically strengthened glass)

[0350] The chemically strengthened glasses of Examples 1 to 16 shown in Tables 1 and 2 were appropriately selected to have the glass compositions shown in the tables in terms of the molar percentage based on the oxide, and were placed in a platinum crucible and heated to a high temperature of 1650° C. or higher by an electric furnace to melt the glass. The glass melt was then poured onto a carbon template and kept at Tg+50° C. for 30 minutes, and then cooled at 0.5° C. / min to obtain a glass block. The obtained glass block was cut, ground, and polished to obtain a plate-shaped glass of 25 mm in length×25 mm in width×0.7 mm in thickness.

[0351] (Production of chemically strengthened glass)

[0352] Next, each of the chemically strengthened glasses of Examples 1 to 14 was subjected to a chemical strengthening treatment under Condition A (in 100 mass % sodium nitrate salt at 380° C. for 4 hours), thereby obtaining a chemically strengthened glass.

[0353] The glass of Example 5 was also subjected to two-step chemical strengthening under the following condition B. (Condition B) First step: 100 mass % sodium nitrate at 380° C. for 100 minutes. Second step: 100 mass % potassium nitrate at 380° C. for 60 minutes.

[0354] The obtained chemically strengthened glass and chemically strengthened glass were evaluated for various properties according to the following procedures.

[0355] [proportion]

[0356] The specific gravity was measured by the Archimedean method.

[0357] [Young's modulus]

[0358] The Young's modulus is measured by an ultrasonic pulse method (JIS R1602, 1995).

[0359] [Stress distribution]

[0360] The stress values ​​were measured using an optical waveguide surface stress meter FSM-6000 and a scattered light photoelastic stress meter SLP2000 manufactured by Orihara Seisakusho. CS0 for two-step stress distribution is the value measured using the optical waveguide surface stress meter FSM-6000, NaCS for one-step stress distribution (CS0 after chemical strengthening treatment at 380°C for 4 hours in 100% by mass sodium nitrate salt) is the value measured using the scattered light photoelastic stress meter SLP2000, and NaDOL (DOC after chemical strengthening treatment at 380°C for 4 hours in 100% by mass sodium nitrate salt) and CS 50 , CS 90These are values ​​obtained using a scattered light photoelastic stress measuring instrument SLP2000.

[0361] [T2 and T4]

[0362] The viscosity of T2 and T4 was measured using a rotational viscometer according to the method specified in ASTM C 965-96 (2017), and the viscosity of each 2 dPa·s or 10 4 dPa·s. It should be noted that NBS710 and NIST717a were used as reference samples for device calibration.

[0363] [K Ic ]

[0364] The fracture toughness value was determined by the DCDC method using the method described in MY He, MR Turner and AG Evans, Acta Metall. Mater. 43 (1995) 3453. Figure 3 The sample of the shape shown and the Tensilon UTA-5kN manufactured by Orient Technology were measured as follows Figure 4 The stress intensity factor K is shown in I (Unit: MPa·m 1 / 2 ) and the crack growth rate v (unit: m / s) I -v curve, using the linear formula to regress and extrapolate the obtained Region III data, and the stress intensity factor K I As the fracture toughness value K Ic .

[0365] [DSC peak temperature, Tg]

[0366] The glass was crushed using an agate mortar, and about 80 mg of the powder was placed in a platinum pool. The heating rate was set to 10 / min, and the temperature was raised from room temperature to 1100°C. A differential scanning calorimeter (manufactured by Bruker; DSC3300SA) was used to measure the DSC curve, and the DSC peak temperature (crystallization peak temperature) and glass transition temperature Tg were calculated.

[0367] [Devitrification temperature]

[0368] The devitrification temperature was determined by the following operation. The glass was crushed, classified using 4 mm mesh and 2 mm mesh sieves, washed with pure water, and then dried to obtain cullet. 2 g to 5 g of cullet was placed on a platinum dish, kept in an electric furnace maintained at a constant temperature for 17 hours, taken out to room temperature air and cooled, and then the operation of observing the presence or absence of devitrification using a polarizing microscope was repeated to estimate the devitrification temperature T.

[0369] [Devitrification viscosity]

[0370] The devitrification viscosity was measured using a rotary high temperature viscometer while decreasing the temperature from 1700°C to 1000°C at 10°C / min (or until the viscosity began to rise sharply due to devitrification), and the viscosity value at the devitrification temperature was taken as the devitrification viscosity logη (dPa·s).

[0371] The results are shown in Tables 1 and 2. In Tables 1 and 2, Examples 1 to 10 and 14 to 16 are embodiments, and Examples 11 to 13 are comparative examples. In Tables 1 and 2, the values ​​in italics are calculated values, and "-" indicates that they are not evaluated. Example 11 has a glass composition within the range of the composition described in International Publication No. 2019 / 108751, Example 12 has a glass composition within the range of the composition described in International Publication No. 2019 / 191480, and Example 13 has a glass composition within the range of the composition described in International Publication No. 2021 / 108314.

[0372] The NaCS and NaDOL in Tables 1 and 2 are stress characteristics of chemically strengthened glasses obtained by chemical strengthening under the above-mentioned condition A. Figure 2 Graph 2 shows the stress distribution of the chemically strengthened glass obtained by subjecting the glass of Example 5 to two-step chemical strengthening under the above-mentioned condition B.

[0373] Under the above condition B Figure 2 The chemically strengthened glass obtained by chemically strengthening the glass of Example 5 shown in the figure shows the following stress characteristics: The plate thickness t is 700 μm.

[0374] (C1) Surface compressive stress CS0: 1287MPa.

[0375] (C2) When the plate thickness is t (μm) and the depth of the compressive stress layer is DOC (μm), DOC / t: 0.17.

[0376] (C3) In the stress distribution in which the vertical axis represents compressive stress (MPa) and the horizontal axis represents depth (μm) from the surface, the average slope in the region of 1 μm to 3 μm from the surface is: -310.

[0377] (C4) In the stress distribution with compressive stress (MPa) on the vertical axis and depth (μm) from the surface on the horizontal axis, the average slope in the region from a depth of 20 μm from the surface to a compressive stress layer depth DOC / 2 μm is: -2.68.

[0378] (C5) When the plate thickness is t (μm), the compressive stress value CS at a depth of 50 μm from the surface is 50 :0.186tMPa.

[0379] (C6) When the plate thickness is t (μm), the compressive stress value CS at a depth of 90 μm from the surface is 90 :0.06tMPa.

[0380]

[0381]

[0382] As shown in Tables 1 and 2, the chemically strengthened glasses of Examples 1 to 10 and 14 as the embodiments have a surface compressive stress of 200 MP to 400 MP and a compressive stress layer depth of 70 μm to 120 μm during chemical strengthening, which exceeds the CT limit and exhibits excellent strengthening characteristics capable of ensuring drop strength. In addition, the chemically strengthened glasses of Examples 1 to 10 have lower T2 and T4 than the comparative examples, and are excellent in productivity.

[0383] The [Al2O3]+[Li2O] content of the chemically strengthened glass of Example 11 is less than 27%, and the content of B2O3 is less than 2%. Compared with the examples, the Young's modulus and K Ic The strengthening characteristics (NaCS) of T2 and T4 are low compared with the examples, and the productivity is poor.

[0384] In the chemically strengthened glass of Example 12, [Li2O] / ([Na2O]+[K2O]) is greater than 3.5, the content of Na2O is less than 2.5%, and the entropy function is less than 0.25.

[0385] Compared with the examples, the NaCS content of the chemically strengthened glass of Example 12 is too high, the stress is too large, and there is a possibility of exceeding the CT limit, which makes it difficult to perform stress design.

[0386] [Al2O3]+[Li2O] of the chemically strengthened glass of Example 13 is less than 27%. Compared with the examples, the chemically strengthened glass of Example 13 has a low Young's modulus and low strengthening characteristics (NaCS). In addition, T2 is higher than that of the examples, and the productivity is poor.

[0387] As described above, the following matters are disclosed in this specification.

[0388] 1. A chemically strengthened glass, comprising, in terms of mol% based on oxides:

[0389] 50%~65% SiO2,

[0390] 15% to 25% Al2O3,

[0391] 2% to 10% B2O3,

[0392] 0%~15% P2O5,

[0393] 0%~15% ZnO,

[0394] 0%~10%MgO,

[0395] 0%~15%CaO,

[0396] 3% to 15% Li2O,

[0397] 2.5% to 15% Na2O,

[0398] 0%~5% K2O,

[0399] 0%~5% ZrO2,

[0400] 0% to 5% Y2O3, and

[0401] 0%~5% TiO2,

[0402] [Li2O] / ([Na2O]+[K2O]) is 0.5 to 3.5,

[0403] [Al2O3]+[Li2O] is 27%~35%.

[0404] In the formula, [ ] represents the content of each component described in parentheses in terms of mol % based on oxides.

[0405] 2. The chemically strengthened glass according to item 1 above, wherein the entropy function S value of the alkali ions obtained from the following formula is 0.25 to 0.40.

[0406] S=-P Li ×log(P Li )-P Na ×log(P Na )-P K ×log(P K )

[0407] P Li =[Li2O] / ([Li2O]+[Na2O]+[K2O])

[0408] PNa =[Na2O] / ([Li2O]+[Na2O]+[K2O])

[0409] P K =[K2O] / ([Li2O]+[Na2O]+[K2O])

[0410] In the formula, [ ] represents the content of each component in parentheses in terms of mol % based on oxides.

[0411] 3. The chemically strengthened glass according to 1 or 2, wherein:

[0412] [SiO2]+[B2O3]+[P2O5] is 50% to 65%,

[0413] [Li2O]+[Na2O]+[K2O] is 14% to 20%,

[0414] [Al2O3]+[B2O3] is 22% to 40%,

[0415] [B2O3]+[P2O5] is 2%~10%.

[0416] In the formula, [ ] represents the content of each component described in parentheses in terms of mol % based on oxides.

[0417] 4. The chemically strengthened glass according to any one of 1 to 3 above, wherein the chemically strengthened glass satisfies the following (A1) to (A4).

[0418] (A1) Young's modulus is 80 GPa to 100 GPa.

[0419] (A2) When the chemically strengthened glass is in the form of a plate having a thickness of 0.7 mm, the surface compressive stress CS0 when chemically strengthened in 100 mass % sodium nitrate salt at 380° C. for 4 hours is 200 MPa to 450 MPa, and the compressive stress layer depth DOC is 70 μm to 120 μm.

[0420] (A3) Viscosity reaches 10 2 dPa·s when the temperature (T2) is below 1650°C and the viscosity reaches 10 4 The temperature (T4) at dPa·s is 1250°C or less.

[0421] (A4) Fracture toughness value K Ic 0.75MPa·m 1 / 2 ~0.85MPa·m 1 / 2 .

[0422] 5. The chemically strengthened glass according to any one of 1 to 4 above, wherein the thickness of the chemically strengthened glass is 0.4 mm to 1.5 mm.

[0423] 6. The chemically strengthened glass according to any one of 1 to 5 above, wherein the thickness of the chemically strengthened glass is 0.4 mm to 1.2 mm.

[0424] 7. A glass comprising, in terms of mole % based on oxides:

[0425] 50%~65% SiO2,

[0426] 15% to 25% Al2O3,

[0427] 2% to 10% B2O3,

[0428] 0%~15% P2O5,

[0429] 0%~15% ZnO,

[0430] 0%~10%MgO,

[0431] 0%~15%CaO,

[0432] 3% to 15% Li2O,

[0433] 2.5% to 15% Na2O,

[0434] 0%~5% K2O,

[0435] 0%~5% ZrO2,

[0436] 0% to 5% Y2O3, and

[0437] 0%~5% TiO2,

[0438] [Li2O] / ([Na2O]+[K2O]) is 0.5 to 3.5,

[0439] [Al2O3]+[Li2O] is 27% to 35%,

[0440] The entropy function S value of the alkali ion represented by the following formula is 0.25 to 0.40.

[0441] S=-P Li ×log(P Li )-P Na ×log(P Na )-P K ×log(P K )

[0442] PLi =[Li2O] / ([Li2O]+[Na2O]+[K2O])

[0443] P Na =[Na2O] / ([Li2O]+[Na2O]+[K2O])

[0444] P K =[K2O] / ([Li2O]+[Na2O]+[K2O])

[0445] In the formula, [ ] represents the content of each component in parentheses in terms of mol % based on oxides.

[0446] 8. The glass according to item 7, wherein, in terms of mol% based on oxides,

[0447] [SiO2]+[B2O3]+[P2O5] is 50% to 65%,

[0448] [Li2O]+[Na2O]+[K2O] is 14% to 20%,

[0449] [Al2O3]+[B2O3] is 22% to 40%,

[0450] [B2O3]+[P2O5] is 2%~10%.

[0451] 9. The glass according to 7 or 8 above, wherein the glass satisfies the following (B1) to (B4).

[0452] (B1) Young's modulus is 80 GPa to 100 GPa.

[0453] (B2) When the glass is in the form of a plate having a thickness of 0.7 mm, the surface compressive stress CS0 when chemically strengthened in 100 mass % sodium nitrate salt at 380° C. for 4 hours is 200 MPa to 450 MPa, and the compressive stress layer depth DOC is 70 μm to 120 μm.

[0454] (B3) Viscosity reaches 10 2 dPa·s when the temperature (T2) is below 1650°C and the viscosity reaches 10 4 The temperature (T4) at dPa·s is 1250°C or less.

[0455] (B4) Fracture toughness value K Ic 0.75MPa·m 1 / 2 ~0.85MPa·m 1 / 2 .

[0456] 10. A glass comprising the chemically strengthened glass according to any one of 1 to 6 above and a compressive stress layer formed therein, wherein:

[0457] The glass has the following stress characteristics (C1) to (C6).

[0458] (C1) The surface compressive stress CS0 is 500 MPa or more.

[0459] (C2) When the plate thickness is t (μm) and the depth of the compressive stress layer is DOC (μm), DOC / t is 0.125 to 0.225.

[0460] (C3) In the stress distribution with compressive stress (MPa) on the vertical axis and depth (μm) from the surface on the horizontal axis, the average slope in the region of 1 μm to 3 μm from the surface is greater than -400 and less than -100.

[0461] (C4) In the stress distribution with compressive stress (MPa) on the vertical axis and depth (μm) from the surface on the horizontal axis, the average slope in the region from a depth of 20 μm from the surface to a depth of the compressive stress layer DOC / 2 μm is greater than -4 and less than -1.5.

[0462] (C5) When the plate thickness is t (μm), the compressive stress value CS at a depth of 50 μm from the surface is 50 It is above 0.1t(MPa).

[0463] (C6) When the plate thickness is t (μm), the compressive stress value CS at a depth of 90 μm from the surface is 90 It is above 0.03t(MPa).

[0464] 11. The glass according to any one of 7 to 9 above, wherein the glass is chemically strengthened glass.

[0465] 12. A Li2O-Al2O3-SiO2-based chemically strengthened glass, wherein:

[0466] The Li2O-Al2O3-SiO2-based chemically strengthened glass contains 2% or more of B2O3, calculated as a mol% based on oxides.

[0467] The Li2O-Al2O3-SiO2-based chemically strengthened glass has a Young's modulus greater than 76 GPa,

[0468] When the Li2O-Al2O3-SiO2-based chemically strengthened glass is chemically strengthened at 380°C for 4 hours in 100% by mass sodium nitrate, the surface compressive stress CS0 is 200 MPa to 450 MPa and the compressive stress layer depth DOC is 70 μm to 120 μm.

[0469] The viscosity of the Li2O-Al2O3-SiO2 chemically strengthened glass reaches 10 2 The temperature (T2) at dPa·s is 1650°C or less.

[0470] 13. A chemically strengthened glass, comprising, in terms of mol% based on oxides:

[0471] 50%~67% SiO2,

[0472] 16% to 25% Al2O3,

[0473] 2% to 10% B2O3,

[0474] 0%~15% P2O5,

[0475] 0%~15% ZnO,

[0476] 0%~10%MgO,

[0477] 0%~15%CaO,

[0478] 3% to 15% Li2O,

[0479] 2.5% to 15% Na2O,

[0480] 0%~5% K2O,

[0481] 0%~5% ZrO2,

[0482] 0% to 5% Y2O3, and

[0483] 0%~5% TiO2,

[0484] [Li2O] / ([Na2O]+[K2O]) is 0.5 to 3.5,

[0485] [Al2O3]+[Li2O] is 22% to 35%,

[0486] The Young's modulus of the chemically strengthened glass is 77 GPa or more.

[0487] In the formula, [ ] represents the content of each component described in parentheses in terms of mol % based on oxides.

[0488] 14. The chemically strengthened glass according to 13 above, wherein the entropy function S value of alkali ions of the chemically strengthened glass obtained by the following formula is 0.25 to 0.40.

[0489] S=-P Li ×log(P Li )-P Na ×log(P Na )-P K ×log(P K )

[0490] P Li =[Li2O] / ([Li2O]+[Na2O]+[K2O])

[0491] P Na =[Na2O] / ([Li2O]+[Na2O]+[K2O])

[0492] P K =[K2O] / ([Li2O]+[Na2O]+[K2O])

[0493] In the formula, [ ] represents the content of each component in parentheses in terms of mol % based on oxides.

[0494] 15. The chemically strengthened glass according to 13 or 14, wherein

[0495] [SiO2]+[B2O3]+[P2O5] is 50% to 69%,

[0496] [Li2O]+[Na2O]+[K2O] is 12% to 20%,

[0497] [Al2O3]+[B2O3] is 19% to 40%,

[0498] [B2O3]+[P2O5] is 2%~10%.

[0499] In the formula, [ ] represents the content of each component described in parentheses in terms of mol % based on oxides.

[0500] 16. The chemically strengthened glass according to 13 or 14, wherein the chemically strengthened glass contains, in terms of mol % based on oxides:

[0501] 56%~65% SiO2,

[0502] 16% to 25% Al2O3,

[0503] 3% to 5% B2O3,

[0504] 0.7% to 1.5% P2O5,

[0505] 0%~15% ZnO,

[0506] MgO greater than 0% and less than or equal to 1.5%,

[0507] 0%~15%CaO,

[0508] 3% to 15% Li2O,

[0509] 2.5% to 15% Na2O,

[0510] K2O greater than 0% and less than or equal to 5%,

[0511] 0%~5% ZrO2,

[0512] 0%~5% Y2O3,

[0513] Greater than 0% and less than or equal to 1% TiO2, and

[0514] 0%~1.2% SrO,

[0515] [Li2O] / ([Na2O]+[K2O]) is 0.5 to 3.5,

[0516] [MgO]+[CaO]+[SrO]+[BaO]+[ZnO] is 1% to 3%,

[0517] [Li2O] / ([Li2O]+[Na2O]+[K2O]) is 0.50 to 0.65,

[0518] [Al2O3]+[Li2O] is 22%~35%.

[0519] In the formula, [ ] represents the content of each component described in parentheses in terms of mol % based on oxides.

[0520] 17. The chemically strengthened glass according to 16, wherein the chemically strengthened glass contains more than 0.1% and less than or equal to 1% of TiO2 in terms of mol% based on oxide.

[0521] 18. The chemically strengthened glass according to 16 or 17, wherein, in terms of mol % based on oxides,

[0522] [Na2O]+[K2O] is 0%~8%.

[0523] In the formula, [ ] represents the content of each component described in parentheses in terms of mol % based on oxides.

[0524] 19. The chemically strengthened glass according to 16 to 18, wherein the content of [MgO] + [CaO] + [SrO] + [BaO] + [ZnO] is 1% to 2.8% in terms of mol% based on oxides.

[0525] In the formula, [ ] represents the content of each component described in parentheses in terms of mol % based on oxides.

[0526] 20. A glass comprising, in terms of mole % on an oxide basis:

[0527] 50%~67% SiO2,

[0528] 16% to 25% Al2O3,

[0529] 2% to 10% B2O3,

[0530] 0%~15% P2O5,

[0531] 0%~15% ZnO,

[0532] 0%~10%MgO,

[0533] 0%~15%CaO,

[0534] 3% to 15% Li2O,

[0535] 2.5% to 15% Na2O,

[0536] 0%~5% K2O,

[0537] 0%~5% ZrO2,

[0538] 0% to 5% Y2O3, and

[0539] 0%~5% TiO2,

[0540] [Li2O] / ([Na2O]+[K2O]) is 0.5 to 3.5,

[0541] [Al2O3]+[Li2O] is 22% to 35%,

[0542] The Young's modulus of the glass is 77 GPa or more,

[0543] The entropy function S value of the alkali ion represented by the following formula is 0.25 to 0.40.

[0544] S=-P Li ×log(P Li )-P Na ×log(P Na )-P K×log(P K )

[0545] P Li =[Li2O] / ([Li2O]+[Na2O]+[K2O])

[0546] P Na =[Na2O] / ([Li2O]+[Na2O]+[K2O])

[0547] P K =[K2O] / ([Li2O]+[Na2O]+[K2O])

[0548] In the formula, [ ] represents the content of each component in parentheses in terms of mol % based on oxides.

[0549] 21. The glass according to 20, wherein, in terms of mol % based on oxides,

[0550] [SiO2]+[B2O3]+[P2O5] is 50% to 69%,

[0551] [Li2O]+[Na2O]+[K2O] is 12% to 20%,

[0552] [Al2O3]+[B2O3] is 19% to 40%,

[0553] [B2O3]+[P2O5] is 2%~10%.

[0554] 22. The glass according to 20 or 21, wherein the glass contains, in terms of mol% based on oxides:

[0555] 56%~65% SiO2,

[0556] 16% to 25% Al2O3,

[0557] 3% to 5% B2O3,

[0558] 0.7% to 1.5% P2O5,

[0559] 0%~15% ZnO,

[0560] MgO greater than 0% and less than or equal to 1.5%,

[0561] 0%~15%CaO,

[0562] 3% to 15% Li2O,

[0563] 2.5% to 15% Na2O,

[0564] K2O greater than 0% and less than or equal to 5%,

[0565] 0%~5% ZrO2,

[0566] 0%~5% Y2O3,

[0567] Greater than 0% and less than or equal to 1% TiO2, and

[0568] 0%~1.2% SrO,

[0569] [Li2O] / ([Na2O]+[K2O]) is 0.5 to 3.5,

[0570] [MgO]+[CaO]+[SrO]+[BaO]+[ZnO] is 1% to 3%,

[0571] [Li2O] / ([Li2O]+[Na2O]+[K2O]) is 0.50 to 0.65,

[0572] [Al2O3]+[Li2O] is 22%~35%.

[0573] In the formula, [ ] represents the content of each component described in parentheses in terms of mol % based on oxides.

[0574] 23. The glass according to any one of 20 to 22, wherein the glass contains greater than 0.1% and less than or equal to 1% TiO2, in terms of mol% based on oxide.

[0575] 24. The glass according to any one of 20 to 23 above, wherein [Na2O]+[K2O] is 0% to 8% in terms of mol% based on oxides.

[0576] In the formula, [ ] represents the content of each component described in parentheses in terms of mol % based on oxides.

[0577] 25. The glass according to any one of 20 to 24, wherein, in terms of mol % based on oxides,

[0578] [MgO]+[CaO]+[SrO]+[BaO]+[ZnO] is 1% to 2.8%.

[0579] In the formula, [ ] represents the content of each component described in parentheses in terms of mol % based on oxides.

[0580] The present invention is described in detail with reference to specific embodiments, but various changes or modifications can be made without departing from the spirit and scope of the present invention, which is obvious to those skilled in the art. It should be noted that this application is based on Japanese patent applications (Japanese patent applications 2022-096854) filed on June 15, 2022 and Japanese patent applications (Japanese patent applications 2022-210494) filed on December 27, 2022, and the entire contents thereof are cited by reference. In addition, all references cited herein are incorporated into this application as a whole.

Claims

1. A chemically strengthened glass, wherein: The chemically strengthened glass contains, in terms of mol% based on oxides: 50%~65% SiO2, 15% to 25% Al2O3, 2% to 10% B2O3, 0%~15% P2O5, 0%~15% ZnO, 0%~10%MgO, 0%~15%CaO, 3% to 15% Li2O, 2.5% to 15% Na2O, 0%~5% K2O, 0%~5% ZrO2, 0% to 5% Y2O3, and 0%~5% TiO2, [Li2O] / ([Na2O]+[K2O]) is 0.5 to 3.5, [Al2O3]+[Li2O] is 27% to 35%, In the formula, [ ] represents the content of each component described in parentheses in terms of mol % based on oxides.

2. The chemically strengthened glass according to claim 1, wherein The entropy function S value of alkali ions obtained by the following formula is 0.25 to 0.40, S=-P Li ×log(P Li )-P Na ×log(P Na )-P K ×log(P K ) P Li =[Li2O] / ([Li2O]+[Na2O]+[K2O]) P Na =[Na2O] / ([Li2O]+[Na2O]+[K2O]) P K =[K2O] / ([Li2O]+[Na2O]+[K2O]) In the formula, [ ] represents the content of each component listed in the brackets in mol % based on the oxide, and the base of log is 10.

3. The chemically strengthened glass according to claim 1, wherein [SiO2]+[B2O3]+[P2O5] is 50% to 65%, [Li2O]+[Na2O]+[K2O] is 14% to 20%, [Al2O3]+[B2O3] is 22% to 40%, [B2O3]+[P2O5] is 2% to 10%, In the formula, [ ] represents the content of each component described in parentheses in terms of mol % based on oxides.

4. The chemically strengthened glass according to any one of claims 1 to 3, wherein The chemically strengthened glass satisfies the following (A1) to (A4), (A1) Young's modulus is 80 GPa to 100 GPa; (A2) when the chemically strengthened glass is in the form of a plate having a thickness of 0.7 mm, the surface compressive stress CS0 when chemically strengthened in 100 mass % sodium nitrate salt at 380° C. for 4 hours is 200 MPa to 450 MPa, and the depth of the compressive stress layer DOC is 70 μm to 120 μm; (A3) Viscosity reaches 10 2 dPa·s when the temperature (T2) is below 1650°C and the viscosity reaches 10 4 dPa·s when the temperature (T4) is below 1250°C; (A4) Fracture toughness value K Ic 0.75MPa·m 1 / 2 ~0.85MPa·m 1 / 2 .

5. The chemically strengthened glass according to any one of claims 1 to 3, wherein The thickness of the chemically strengthened glass is 0.4 mm to 1.5 mm.

6. The chemically strengthened glass according to any one of claims 1 to 3, wherein The thickness of the chemically strengthened glass is 0.4 mm to 1.2 mm.

7. A glass, wherein: The glass contains, in mole % based on oxides: 50%~65% SiO2, 15% to 25% Al2O3, 2% to 10% B2O3, 0%~15% P2O5, 0%~15% ZnO, 0%~10%MgO, 0%~15%CaO, 3% to 15% Li2O, 2.5% to 15% Na2O, 0%~5% K2O, 0%~5% ZrO2, 0% to 5% Y2O3, and 0%~5% TiO2, [Li2O] / ([Na2O]+[K2O]) is 0.5 to 3.5, [Al2O3]+[Li2O] is 27% to 35%, The entropy function S of alkali ions expressed by the following formula has a value of 0.25 to 0.40, S=-P Li ×log(P Li )-P Na ×log(P Na )-P K ×log(P K ) P Li =[Li2O] / ([Li2O]+[Na2O]+[K2O]) P Na =[Na2O] / ([Li2O]+[Na2O]+[K2O]) P K =[K2O] / ([Li2O]+[Na2O]+[K2O]) In the formula, [ ] represents the content of each component listed in the brackets in mol % based on the oxide, and the base of log is 10.

8. The glass according to claim 7, wherein: In terms of mole % based on oxide, [SiO2]+[B2O3]+[P2O5] is 50% to 65%, [Li2O]+[Na2O]+[K2O] is 14% to 20%, [Al2O3]+[B2O3] is 22% to 40%, [B2O3]+[P2O5] is 2%~10%.

9. The glass according to claim 7 or 8, wherein: The glass satisfies the following (B1) to (B4): (B1) Young's modulus is 80 GPa to 100 GPa; (B2) When the glass is in the form of a plate having a thickness of 0.7 mm, the surface compressive stress CS0 when chemically strengthened in 100 mass % sodium nitrate salt at 380° C. for 4 hours is 200 MPa to 450 MPa, and the depth of the compressive stress layer DOC is 70 μm to 120 μm; (B3) Viscosity reaches 10 2 dPa·s when the temperature (T2) is below 1650°C and the viscosity reaches 10 4 dPa·s when the temperature (T4) is below 1250°C; (B4) Fracture toughness value K Ic 0.75MPa·m 1 / 2 ~0.85MPa·m 1 / 2 .

10. A glass comprising the chemically strengthened glass according to any one of claims 1 to 3 in which a compressive stress layer is formed, wherein: The glass has the following stress characteristics (C1) to (C6): (C1) Surface compressive stress CS0 is greater than 500 MPa; (C2) When the plate thickness is t (μm) and the depth of the compressive stress layer is DOC (μm), DOC / t is 0.125 to 0.225; (C3) in a stress distribution in which the vertical axis represents compressive stress (MPa) and the horizontal axis represents depth (μm) from the surface, the average slope in a region of 1 μm to 3 μm from the surface is greater than −400 and less than −100; (C4) in a stress distribution in which the vertical axis represents compressive stress (MPa) and the horizontal axis represents depth (μm) from the surface, the average slope in a region from a depth of 20 μm from the surface to a depth of the compressive stress layer DOC / 2 μm is greater than −4 and less than −1.5; (C5) When the plate thickness is t (μm), the compressive stress value CS at a depth of 50 μm from the surface is 50 0.1t(MPa) or more; (C6) When the plate thickness is t (μm), the compressive stress value CS at a depth of 90 μm from the surface is 90 It is above 0.03t(MPa).

11. The glass according to claim 7 or 8, wherein: The glass is chemically strengthened glass.

12. A Li2O-Al2O3-SiO2-based chemically strengthened glass, wherein: The Li2O-Al2O3-SiO2-based chemically strengthened glass contains 2% or more of B2O3, calculated as a mol% based on oxides. The Li2O-Al2O3-SiO2-based chemically strengthened glass has a Young's modulus greater than 76 GPa, When the Li2O-Al2O3-SiO2-based chemically strengthened glass is chemically strengthened at 380°C for 4 hours in 100% by mass sodium nitrate, the surface compressive stress CS0 is 200 MPa to 450 MPa and the compressive stress layer depth DOC is 70 μm to 120 μm. The viscosity of the Li2O-Al2O3-SiO2 chemically strengthened glass reaches 10 2 The temperature (T2) at dPa·s is 1650°C or less.

13. A chemically strengthened glass, wherein: The chemically strengthened glass contains, in terms of mol% based on oxides: 50%~67% SiO2, 16% to 25% Al2O3, 2% to 10% B2O3, 0%~15% P2O5, 0%~15% ZnO, 0%~10%MgO, 0%~15%CaO, 3% to 15% Li2O, 2.5% to 15% Na2O, 0%~5% K2O, 0%~5% ZrO2, 0% to 5% Y2O3, and 0%~5% TiO2, [Li2O] / ([Na2O]+[K2O]) is 0.5 to 3.5, [Al2O3]+[Li2O] is 22% to 35%, The Young's modulus of the chemically strengthened glass is 77 GPa or more. In the formula, [ ] represents the content of each component described in parentheses in terms of mol % based on oxides.

14. The chemically strengthened glass according to claim 13, wherein The entropy function S value of the alkali ions of the chemically strengthened glass obtained by the following formula is 0.25 to 0.40: S=-P Li ×log(P Li )-P Na ×log(P Na )-P K ×log(P K ) P Li =[Li2O] / ([Li2O]+[Na2O]+[K2O]) P Na =[Na2O] / ([Li2O]+[Na2O]+[K2O]) P K =[K2O] / ([Li2O]+[Na2O]+[K2O]) In the formula, [ ] represents the content of each component listed in the brackets in mol % based on the oxide, and the base of log is 10.

15. The chemically strengthened glass according to claim 13 or 14, wherein [SiO2]+[B2O3]+[P2O5] is 50% to 69%, [Li2O]+[Na2O]+[K2O] is 12% to 20%, [Al2O3]+[B2O3] is 19% to 40%, [B2O3]+[P2O5] is 2% to 10%, In the formula, [ ] represents the content of each component described in parentheses in terms of mol % based on oxides.

16. The chemically strengthened glass according to claim 13 or 14, wherein: The chemically strengthened glass contains, in terms of mol% based on oxides: 56%~65% SiO2, 16% to 25% Al2O3, 3% to 5% B2O3, 0.7% to 1.5% P2O5, 0%~15% ZnO, MgO greater than 0% and less than or equal to 1.5%, 0%~15%CaO, 3% to 15% Li2O, 2.5% to 15% Na2O, K2O greater than 0% and less than or equal to 5%, 0%~5% ZrO2, 0%~5% Y2O3, Greater than 0% and less than or equal to 1% TiO2, and 0%~1.2% SrO, [Li2O] / ([Na2O]+[K2O]) is 0.5 to 3.5, [MgO]+[CaO]+[SrO]+[BaO]+[ZnO] is 1% to 3%, [Li2O] / ([Li2O]+[Na2O]+[K2O]) is 0.50 to 0.65, [Al2O3]+[Li2O] is 22% to 35%, In the formula, [ ] represents the content of each component described in parentheses in terms of mol % based on oxides.

17. The chemically strengthened glass according to claim 16, wherein: The chemically strengthened glass contains greater than 0.1% and less than or equal to 1% of TiO 2 in terms of mol % based on oxide.

18. The chemically strengthened glass according to claim 16, wherein In terms of mole % based on oxide, [Na2O]+[K2O] is 0% to 8%, In the formula, [ ] represents the content of each component described in parentheses in terms of mol % based on oxides.

19. The chemically strengthened glass according to claim 16, wherein: In terms of mole % based on oxides, [MgO]+[CaO]+[SrO]+[BaO]+[ZnO] is 1% to 2.8%, In the formula, [ ] represents the content of each component described in parentheses in terms of mol % based on oxides.

20. A glass, wherein: The glass contains, in mole % based on oxides: 50%~67% SiO2, 16% to 25% Al2O3, 2% to 10% B2O3, 0%~15% P2O5, 0%~15% ZnO, 0%~10%MgO, 0%~15%CaO, 3% to 15% Li2O, 2.5% to 15% Na2O, 0%~5% K2O, 0%~5% ZrO2, 0% to 5% Y2O3, and 0%~5% TiO2, [Li2O] / ([Na2O]+[K2O]) is 0.5 to 3.5, [Al2O3]+[Li2O] is 22% to 35%, The Young's modulus of the glass is 77 GPa or more, The entropy function S of alkali ions expressed by the following formula has a value of 0.25 to 0.40, S=-P Li ×log(P Li )-P Na ×log(P Na )-P K ×log(P K ) P Li =[Li2O] / ([Li2O]+[Na2O]+[K2O]) P Na =[Na2O] / ([Li2O]+[Na2O]+[K2O]) P K =[K2O] / ([Li2O]+[Na2O]+[K2O]) In the formula, [ ] represents the content of each component listed in the brackets in mol % based on the oxide, and the base of log is 10.

21. The glass according to claim 20, wherein: In terms of mole % based on oxide, [SiO2]+[B2O3]+[P2O5] is 50% to 69%, [Li2O]+[Na2O]+[K2O] is 12% to 20%, [Al2O3]+[B2O3] is 19% to 40%, [B2O3]+[P2O5] is 2%~10%.

22. The glass according to claim 20 or 21, wherein: The glass contains, in mole % based on oxides: 56%~65% SiO2, 16% to 25% Al2O3, 3% to 5% B2O3, 0.7% to 1.5% P2O5, 0%~15% ZnO, MgO greater than 0% and less than or equal to 1.5%, 0%~15%CaO, 3% to 15% Li2O, 2.5% to 15% Na2O, K2O greater than 0% and less than or equal to 5%, 0%~5% ZrO2, 0%~5% Y2O3, Greater than 0% and less than or equal to 1% TiO2, and 0%~1.2% SrO, [Li2O] / ([Na2O]+[K2O]) is 0.5 to 3.5, [MgO]+[CaO]+[SrO]+[BaO]+[ZnO] is 1% to 3%, [Li2O] / ([Li2O]+[Na2O]+[K2O]) is 0.50 to 0.65, [Al2O3]+[Li2O] is 22% to 35%, In the formula, [ ] represents the content of each component described in parentheses in terms of mol % based on oxides.

23. The glass according to claim 22, wherein: The glass contains greater than 0.1% and less than or equal to 1% TiO2, measured as a mole % on an oxide basis.

24. The glass according to claim 22, wherein: In terms of mole % based on oxides, [Na2O]+[K2O] is 0% to 8%, In the formula, [ ] represents the content of each component described in parentheses in terms of mol % based on oxides.

25. The glass according to claim 22, wherein: In terms of mole % based on oxide, [MgO]+[CaO]+[SrO]+[BaO]+[ZnO] is 1% to 2.8%, In the formula, [ ] represents the content of each component described in parentheses in terms of mol % based on oxides.

Citation Information

Patent Citations

  • A two-step method for strengthening glass

    JP2013536155A

  • Cationic electrodeposition coating composition

    JP2022096854A

  • Glasses with low excess modifier content

    WO2019108751A1

  • Glasses having high fracture toughness

    WO2019191480A1